Resin composition, cured product, laminate, transparent antenna, and image display device

The resin composition, featuring styrene block copolymers and (meth)acrylic compounds, addresses mechanical and dielectric weaknesses in transparent antennas by providing high tensile modulus and low dielectric properties, enhancing durability and efficiency in high-frequency communication.

CN119156422APending Publication Date: 2024-12-17RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380029433.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-10
Filing Date
2023-03-29
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing transparent antennas lack sufficient mechanical strength and dielectric properties, particularly in high-frequency communication applications, necessitating improved resin compositions for durable and efficient operation.

Method used

A resin composition comprising a styrene block copolymer, a (meth)acrylic compound, and a polymerization initiator, specifically formulated to achieve high tensile modulus and low dielectric properties through the use of styrene-butadiene-styrene block copolymers and alkanediol di(meth)acrylates, with optional conductive components like copper.

Benefits of technology

The composition enables the production of cured products with high tensile elastic modulus and excellent dielectric properties, including low relative dielectric constant and dielectric loss tangent, suitable for high-frequency communication and transparent antenna applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156422A_ABST
    Figure CN119156422A_ABST
Patent Text Reader

Abstract

A resin composition containing a styrene block copolymer, a (meth) acrylic compound, and a polymerization initiator. A laminate provided with a base film and a transparent resin layer disposed on the base film, the transparent resin layer containing at least one substance selected from the group consisting of the resin composition and a cured product thereof. A transparent antenna (110) is provided with a transparent substrate (110a), a conductive member (110b) disposed on the transparent substrate (110a), and a coating member (110c) disposed on the conductive member (110b), and at least one member selected from the group consisting of the transparent substrate (110a) and the coating member (110c) contains a cured product of the resin composition. An image display device (100) is provided with a transparent antenna (110).
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0002] The antenna for receiving radio waves is provided in an image display device (for example, an image display device in various electronic devices such as a personal computer, a navigation system, a mobile phone, a clock, an electronic dictionary, etc.), a component of a car, a building, etc. For example, an image display device with a built-in antenna is sometimes used. In recent years, in order to correspond to the miniaturization, thinning, and diversification of shapes of image display devices and ensure the likelihood of design, it has been proposed to configure a transparent and low-visibility antenna (hereinafter also referred to as a "transparent antenna") on the image display portion for displaying images. Various components have been studied for components for obtaining a transparent antenna (for example, refer to the following patent document 1).

[0003] Previous technical literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-091788 Summary of the invention

[0006] Technical issues to be solved by the invention

[0007] As a component of a transparent antenna, a cured product of a resin composition is sometimes used. From the viewpoint of maintaining sufficient durability, such a cured product is required to have high mechanical strength, for example, a high tensile modulus.

[0008] One aspect of the present invention is to provide a resin composition capable of obtaining a cured product having a high tensile modulus of elasticity. Another aspect of the present invention is to provide a cured product of the resin composition. Another aspect of the present invention is to provide a laminate using the resin composition or its cured product. Another aspect of the present invention is to provide a transparent antenna using the cured product of the resin composition. Another aspect of the present invention is to provide an image display device using the transparent antenna.

[0009] Means for solving technical problems

[0010] The present invention is related to the following [1] to

[19] in several aspects.

[0011] [1] A resin composition comprising a styrene block copolymer, a (meth)acrylic compound and a polymerization initiator.

[0012] [2] The resin composition according to [1], wherein the styrene-based block copolymer comprises a styrene-butadiene-styrene block copolymer.

[0013] [3] The resin composition according to [1] or [2], wherein the content of the styrene block copolymer is 50% by mass or more based on the total mass of the resin composition.

[0014] [4] The resin composition according to any one of [1] to [3], wherein the (meth)acrylic compound contains a methacrylic compound.

[0015] [5] The resin composition according to any one of [1] to [4], wherein the (meth)acrylic compound contains alkanediol di(meth)acrylate.

[0016] [6] The resin composition according to any one of [1] to [5], wherein the (meth)acrylic compound contains alkanediol dimethacrylate.

[0017] [7] The resin composition according to any one of [1] to [6], wherein the (meth)acrylic compound includes a compound represented by the following general formula (I).

[0018]

[0019] [Where R 1 represents a group containing 9 or less carbon atoms and 2 or more oxygen atoms, R 2a and R 2b Each independently represents a hydrogen atom or a methyl group.]

[0020] [8] The resin composition according to [7], wherein the (meth)acrylic compound comprises R 2a and R 2b A compound wherein at least one of the radicals is a methyl group.

[0021] [9] The resin composition according to any one of [1] to [8], wherein the content of the (meth)acrylic compound is 1 to 300 parts by mass based on 100 parts by mass of the styrene block copolymer.

[0022]

[10] The resin composition according to any one of [1] to [9], wherein the polymerization initiator contains a peroxide.

[0023]

[11] The resin composition according to any one of [1] to

[10] , wherein the polymerization initiator contains a peroxyester.

[0024]

[12] A cured product, which is a cured product of the resin composition according to any one of [1] to

[11] .

[0025]

[13] A laminate comprising a substrate film and a transparent resin layer disposed on the substrate film, wherein the transparent resin layer comprises at least one selected from the group consisting of the resin composition described in any one of [1] to

[11] and a cured product thereof.

[0026]

[14] The laminate according to

[13] , further comprising a conductive member disposed on the transparent resin layer.

[0027]

[15] The laminate according to

[14] , wherein the conductive member contains copper.

[0028]

[16] The laminate according to

[14] or

[15] , wherein the thickness of the conductive member is 5 μm or less.

[0029]

[17] A transparent antenna comprising a transparent substrate, a conductive component disposed on the transparent substrate, and a covering component disposed on the conductive component, wherein at least one selected from the group consisting of the transparent substrate and the covering component comprises a cured product of the resin composition described in any one of [1] to

[11] .

[0030]

[18] The transparent antenna according to

[17] , wherein the conductive member has a mesh portion.

[0031]

[19] The transparent antenna according to

[17] or

[18] , wherein the conductive component contains copper.

[0032]

[20] An image display device comprising the transparent antenna described in any one of

[17] to

[19] .

[0033] Effects of the Invention

[0034] According to one aspect of the present invention, a resin composition capable of obtaining a cured product having a high tensile elastic modulus can be provided. According to another aspect of the present invention, a cured product of the resin composition can be provided. According to another aspect of the present invention, a laminate using the resin composition or its cured product can be provided. According to another aspect of the present invention, a transparent antenna using the cured product of the resin composition can be provided. According to another aspect of the present invention, an image display device using the transparent antenna can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic cross-sectional view showing an example of a laminated body.

[0036] Figure 2 It is a schematic cross-sectional view showing an example of a laminated body.

[0037] Figure 3 It is a schematic cross-sectional view showing an example of an image display device.

[0038] Figure 4 It is a schematic cross-sectional view showing an example of an image display device. DETAILED DESCRIPTION

[0039] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.

[0040] In this specification, the numerical range shown by "~" indicates the range including the numerical values ​​recorded before and after "~" as the minimum and maximum values, respectively. "Above A" in the numerical range refers to A and the range exceeding A. "Below A" in the numerical range refers to A and the range less than A. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of other stages. In the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. "A or B" can include either A and B, or both. The materials exemplified in this specification are not particularly limited, and can be used alone or in combination of two or more. In this specification, with respect to the content of each component in the composition, when there are multiple substances that meet the various components in the composition, unless otherwise specified, it refers to the total amount of the multiple substances present in the composition. With respect to the term "layer", in addition to the structure of the shape formed on the entire surface when observed in a top view, it also includes the structure of the shape formed in a part. The term "process" includes independent processes, even if they cannot be clearly distinguished from other processes, as long as the intended effect of the process can be achieved. "(Meth)acrylate" refers to at least one of acrylate and its corresponding methacrylate. The same applies to other similar expressions such as "(meth)acrylic acid". The content of (meth)acrylic acid-based compounds refers to the total amount of acrylic acid-based compounds and methacrylic acid-based compounds. Hydroxyl groups do not include OH groups included in carboxyl groups.

[0041] The resin composition involved in the present embodiment contains a styrene block copolymer, a (meth) acrylic compound and a polymerization initiator. The resin composition involved in the present embodiment can be used as a resin composition for a transparent antenna. The resin composition involved in the present embodiment can be used as a thermosetting resin composition, and can also be used as a photocurable resin composition. The cured product involved in the present embodiment is obtained by curing the resin composition involved in the present embodiment, and is a cured product of the resin composition involved in the present embodiment. The cured product involved in the present embodiment can be in a semi-cured state or a fully cured state.

[0042] According to the resin composition involved in the present embodiment, it is possible to obtain a cured product with a high tensile modulus of elasticity. According to the resin composition involved in the present embodiment, in the evaluation method described in the embodiment described later, it is possible to obtain a tensile modulus of elasticity of more than 50MPa (preferably more than 100MPa, more than 150MPa, more than 200MPa, etc.). It is inferred that by interacting between molecules through the block chains consisting of the monomer units derived from styrene compounds, it is possible to obtain a cured product with a high tensile modulus of elasticity. However, the main reason for obtaining a high tensile modulus of elasticity is not limited to this content.

[0043] According to one aspect of the resin composition according to the present embodiment, a cured product having a high tensile elastic modulus and excellent transparency can be obtained.

[0044] Transparent antenna can be used in the communication of high frequency band for realizing high-speed and large-capacity communication. In the communication of high frequency band, there is a tendency that the transmission loss is large. Therefore, as a component of transparent antenna, the cured product of resin composition is required to have excellent dielectric properties. According to one mode of the resin composition involved in the present embodiment, a cured product with excellent relative dielectric constant (low relative dielectric constant) can be obtained. According to one mode of the resin composition involved in the present embodiment, in the evaluation method described in the embodiment described later, for example, a relative dielectric constant of less than 3.0 (preferably less than 2.8, less than 2.6, less than 2.5, etc.) can be obtained. And, according to one mode of the resin composition involved in the present embodiment, a cured product with excellent dielectric loss tangent (low dielectric loss tangent) can be obtained. According to one aspect of the resin composition involved in the present embodiment, in the evaluation method described in the examples described below, for example, a dielectric loss tangent of 0.0060 or less (preferably 0.0050 or less, 0.0045 or less, 0.0040 or less, 0.0035 or less, 0.0030 or less, etc.) can be obtained.

[0045] The resin composition involved in the present embodiment contains a styrene block copolymer. A styrene block copolymer is a block copolymer having a styrene compound as a monomer unit (a block copolymer having a monomer unit derived from a styrene compound). A styrene block copolymer can be a block copolymer having a monomer unit of a styrene compound and a monomer unit of another styrene compound, or a block copolymer having a monomer unit of a styrene compound and a monomer unit of a compound not corresponding to the styrene compound. A styrene block copolymer can be an elastomer.

[0046] Examples of the styrene compound include styrene; alkyl styrenes such as methyl styrene, dimethyl styrene, trimethyl styrene, ethyl styrene, diethyl styrene, triethyl styrene, propyl styrene, butyl styrene, hexyl styrene, heptyl styrene, and octyl styrene; halogenated styrenes such as fluorostyrene, chlorostyrene, bromostyrene, dibromostyrene, and iodostyrene; nitrostyrene; acetylstyrene; methoxystyrene, etc. From the viewpoint of easily obtaining a high tensile modulus of elasticity in a cured product and the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in a cured product, the styrene block copolymer may have styrene as a monomer unit.

[0047] As styrene block copolymers, styrene-butadiene-styrene block copolymers, styrene-butylene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-ethylene-butylene-styrene block copolymers, styrene-ethylene-propylene-styrene block copolymers, these hydrogenated copolymers, etc. can be cited. From the viewpoint of easily obtaining a high tensile modulus of elasticity in a cured product, styrene block copolymers can include styrene-butadiene-styrene block copolymers. It is inferred that by interacting between molecules by the block chains composed of monomer units derived from butadiene, a high tensile modulus of elasticity is easily obtained in a cured product. However, the main reason for easily obtaining a high tensile modulus of elasticity is not limited to the content. In addition, by using styrene-butadiene-styrene block copolymers, when the resin composition involved in the present embodiment is cured under a state where the resin composition is in contact with a conductive component (such as a copper component), it is easy to suppress the generation of wrinkles on the conductive component.

[0048] Styrene block copolymers may be modified by carboxylic anhydride or may not be modified by carboxylic anhydride. As carboxylic anhydride, dicarboxylic anhydride such as maleic anhydride, phthalic anhydride, itaconic anhydride, etc. may be cited. From the viewpoint of easily obtaining a cured product with high adhesion to a conductive component, the styrene block copolymer may include a styrene block copolymer modified by carboxylic anhydride, a styrene block copolymer modified by maleic anhydride, a styrene-butadiene-styrene block copolymer modified by carboxylic anhydride, or a styrene-butadiene-styrene block copolymer modified by maleic anhydride. From the viewpoint of easily obtaining a high tensile elastic modulus in a cured product, the styrene block copolymer may include a styrene block copolymer not modified by carboxylic anhydride, a styrene block copolymer not modified by maleic anhydride, a styrene-butadiene-styrene block copolymer not modified by carboxylic anhydride, or a styrene-butadiene-styrene block copolymer not modified by maleic anhydride.

[0049] From the viewpoint of being easy to obtain high tensile modulus of elasticity in a cured product and being easy to obtain excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in a cured product, based on the total mass of styrene block copolymers, the content of the monomeric unit of styrene compounds or the content of the monomeric unit of styrene can be within the following range. The content of the monomeric unit can be more than 5% by mass, more than 10% by mass, more than 15% by mass, more than 20% by mass, more than 25% by mass, more than 30% by mass, more than 35% by mass or more than 40% by mass. The content of the monomeric unit can be less than 80% by mass, less than 75% by mass, less than 70% by mass, less than 65% by mass, less than 60% by mass, less than 55% by mass, less than 50% by mass, less than 45% by mass or less than 40% by mass. From these viewpoints, the content of the monomer unit may be 5-80 mass %, 5-60 mass %, 5-50 mass %, 20-80 mass %, 20-60 mass %, 20-50 mass %, 30-80 mass %, 30-60 mass % or 30-50 mass %.

[0050] From the viewpoint of easily obtaining a high tensile modulus of elasticity in a cured product and from the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in a cured product, the content of the styrene block copolymer may be 50% by mass or more, more than 50% by mass, 70% by mass or more, 90% by mass or more, 95% by mass or more, or 99% by mass or more, based on the total mass of the polymer (the total amount of the polymer contained in the resin composition). The polymer contained in the resin composition may be substantially formed of a styrene block copolymer (based on the total mass of the polymer contained in the resin composition, the content of the styrene block copolymer is substantially 100% by mass).

[0051] The MFR (melt flow rate. 200°C, 5 kgf (49N). Unit: g / 10 min) of the styrene block copolymer measured according to ISO 1133 can be within the following range. From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the MFR of the styrene block copolymer can be 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, or 6 or more. The MFR of the styrene block copolymer can be 7 or more. From the viewpoint of easily obtaining a high tensile modulus in the cured product, the MFR of the styrene block copolymer can be 10 or less, 9 or less, 8 or less, 7 or less, or 6 or less. The MFR of the styrene block copolymer can be 5 or less. From these viewpoints, the MFR of the styrene block copolymer can be 1 to 10, 3 to 8, 5 to 7, 4 to 6, or 6 to 8.

[0052] The Vicat softening temperature of the styrene block copolymer measured according to ISO 306 (test load 10N, heating rate 50°C / h) can be within the following ranges. The Vicat softening temperature of the styrene block copolymer can be 50°C or more, 60°C or more, 70°C or more, 72°C or more, 75°C or more, 80°C or more, 81°C or more, or 83°C or more. From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the Vicat softening temperature of the styrene block copolymer can be 100°C or less, 90°C or less, 85°C or less, 83°C or less, 81°C or less, 80°C or less, 75°C or less, or 72°C or less. From these viewpoints, the Vicat softening temperature of the styrene block copolymer can be 50-100°C, 60-90°C, or 70-85°C.

[0053] As the content of the polymer (polymer contained in the resin composition) or the content of the styrene block copolymer, from the viewpoint of easily obtaining a high tensile modulus in the cured product and from the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content A can be within the following ranges based on the total mass of the resin composition (excluding the mass of the organic solvent), the total amount of the polymer (polymer contained in the resin composition), the (meth)acrylic compound and the polymerization initiator, the total amount of the polymer (polymer contained in the resin composition), the methacrylic compound and the polymerization initiator, the total amount of the styrene block copolymer, the (meth)acrylic compound and the polymerization initiator, the total amount of the styrene block copolymer, the methacrylic compound and the polymerization initiator, the total amount of the polymer (polymer contained in the resin composition) and the (meth)acrylic compound, the total amount of the polymer (polymer contained in the resin composition) and the methacrylic compound, the total amount of the styrene block copolymer and the (meth)acrylic compound, or the total amount of the styrene block copolymer and the methacrylic compound. The content A may be 20% by mass or more, more than 20% by mass, 30% by mass or more, more than 30% by mass, 40% by mass or more, more than 40% by mass, 50% by mass or more, more than 50% by mass, 60% by mass or more, 65% by mass or more, 70% by mass or more, 75% by mass or more, 78% by mass or more, or 80% by mass or more. The content A may be 99% by mass or less, 95% by mass or less, 90% by mass or less, 85% by mass or less, 82% by mass or less, or 80% by mass or less. From these viewpoints, the content A may be 20 to 99% by mass, 20 to 90% by mass, 20 to 85% by mass, 50 to 99% by mass, 50 to 90% by mass, 50 to 85% by mass, 70 to 99% by mass, 70 to 90% by mass, or 70 to 85% by mass.

[0054] The resin composition according to the present embodiment may contain a (meth)acrylic compound. The (meth)acrylic compound is a compound having a (meth)acryloyl group. The (meth)acrylic compound may or may not have an epoxy group.

[0055] The (meth)acrylic compound may include at least one selected from the group consisting of a monofunctional (meth)acrylic compound and a polyfunctional (meth)acrylic compound (a bifunctional (meth)acrylic compound or a trifunctional or higher (meth)acrylic compound). For example, a "bifunctional (meth)acrylic compound" refers to a compound having a total of two acryloyl groups and two methacryloyl groups in one molecule. From the viewpoint of easily obtaining a high tensile modulus of elasticity in a cured product and obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in a cured product, the (meth)acrylic compound may include a bifunctional (meth)acrylic compound.

[0056] Examples of the monofunctional (meth)acrylic acid compound include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, butoxyethyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octylheptyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, and (meth)acrylate. aliphatic (meth)acrylates such as stearyl (meth)acrylate, behenyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, and mono(2-(meth)acryloyloxyethyl)succinate; cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and (meth)acrylate. alicyclic (meth)acrylates such as isobornyl (meth)acrylate, mono(2-(meth)acryloyloxyethyl)tetrahydrophthalic acid, mono(2-(meth)acryloyloxyethyl)hexahydrophthalic acid; benzyl (meth)acrylate, phenyl (meth)acrylate, o-biphenyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, p-isopropylphenylphenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, 1-naphthyloxyethyl (meth)acrylate, 2-naphthyloxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate Aromatic (meth)acrylates such as esters, (meth)acrylate phenoxypolypropylene glycol ester, (meth)acrylate 2-hydroxy-3-phenoxypropyl ester, (meth)acrylate 2-hydroxy-3-(o-phenylphenoxy)propyl ester, (meth)acrylate 2-hydroxy-3-(1-naphthyloxy)propyl ester, (meth)acrylate 2-hydroxy-3-(2-naphthyloxy)propyl ester; heterocyclic (meth)acrylates such as (meth)acrylate 2-tetrahydrofurfuryl ester, N-(meth)acryloyloxyethyl hexahydrophthalimide, 2-(meth)acryloyloxyethyl-N-carbazole; (meth)acryloyl group-containing phosphates (e.g., (meth)acryloyloxyethyl acid phosphate); these caprolactone modified products, etc.

[0057] Examples of the bifunctional (meth)acrylic compound include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1 aliphatic (meth)acrylates (e.g., alkanediol di(meth)acrylates) such as 6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, nonanediol di(meth)acrylate (e.g., 1,9-nonanediol di(meth)acrylate), decanediol di(meth)acrylate (e.g., 1,10-decanediol di(meth)acrylate), dodecanediol di(meth)acrylate (e.g., 1,12-dodecanediol di(meth)acrylate), glycerol di(meth)acrylate, ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate, and the like; cyclohexanedimethanol di(meth)acrylate, ethoxylated cyclohexanedimethanol di(meth)acrylate, and the like; acrylate, propoxylated cyclohexanedimethanol di(meth)acrylate, ethoxylated propoxylated cyclohexanedimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethoxylated tricyclodecane dimethanol di(meth)acrylate, propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated hydrogenated bisphenol A di(meth)acrylate, propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated hydrogenated bisphenol F di(meth)acrylate, propoxylated hydrogenated bisphenol F di(meth)acrylate, ethoxylated propoxylated hydrogenated bisphenol F di(meth)acrylate Alicyclic (meth)acrylates such as acrylates; aromatic (meth)acrylates such as ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated bisphenol AF di(meth)acrylate, propoxylated bisphenol AF di(meth)acrylate, ethoxylated propoxylated bisphenol AF di(meth)acrylate, ethoxylated fluorene di(meth)acrylate, propoxylated fluorene di(meth)acrylate, and ethoxylated propoxylated fluorene di(meth)acrylate;Heterocyclic (meth)acrylates such as dioxypropylene glycol di(meth)acrylate, ethoxylated isocyanuric acid di(meth)acrylate, propoxylated isocyanuric acid di(meth)acrylate, and ethoxylated propoxylated isocyanuric acid di(meth)acrylate; these caprolactone modified products; aliphatic epoxy (meth)acrylates such as neopentyl glycol epoxy (meth)acrylate; alicyclic epoxy (meth)acrylates such as cyclohexanedimethanol epoxy (meth)acrylate, hydrogenated bisphenol A epoxy (meth)acrylate, and hydrogenated bisphenol F epoxy (meth)acrylate; aromatic epoxy (meth)acrylates such as resorcinol epoxy (meth)acrylate, bisphenol A epoxy (meth)acrylate, bisphenol F epoxy (meth)acrylate, bisphenol AF epoxy (meth)acrylate, and fluorene epoxy (meth)acrylate, etc.;

[0058] Examples of the trifunctional or higher-functional (meth)acrylic compound include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and ethoxylated propoxylated pentaerythritol tri(meth)acrylate. Aliphatic (meth)acrylates such as oxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, and propoxylated dipentaerythritol hexa(meth)acrylate; heterocyclic (meth)acrylates such as ethoxylated isocyanurate tri(meth)acrylate, propoxylated isocyanurate tri(meth)acrylate, and ethoxylated propoxylated isocyanurate tri(meth)acrylate; these caprolactone modified products; aromatic epoxy (meth)acrylates such as phenol novolac type epoxy (meth)acrylate and cresol novolac type epoxy (meth)acrylate, etc.

[0059] From the viewpoint of easily obtaining high tensile modulus in cured product and obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in cured product, (meth) acrylic acid compounds can include aliphatic (meth) acrylate. From the viewpoint of easily obtaining high tensile modulus in cured product and obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in cured product, (meth) acrylic acid compounds can include alkanediol di(meth) acrylate, alkanediol dimethacrylate, at least one selected from the group consisting of nonanediol di(meth) acrylate and dodecanediol di(meth) acrylate, at least one selected from the group consisting of nonanediol dimethacrylate and dodecanediol dimethacrylate. (Meth) acrylic acid compounds can include acrylic acid compounds (compounds with acryloyl). From the viewpoint of easily obtaining low dielectric loss tangent in cured product, (meth) acrylic acid compounds can include methacrylic acid compounds (compounds with methacryloyl). It is speculated that the methacrylic compound has a methyl group in the methacryloyl group, which suppresses the molecular vibration associated with polarization and increases the hydrophobicity of the molecule, thereby obtaining a cured product with a low dielectric loss tangent. However, the main reason for obtaining a low dielectric loss tangent is not limited to this content. The methacrylic compound may or may not have an acryloyl group.

[0060] From the viewpoint of facilitating adjustment of dielectric properties (relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the (meth)acrylic compound may contain a compound represented by the following general formula (I).

[0061]

[0062] In the formula, R 1 represents a group containing 9 or less carbon atoms and 2 or more oxygen atoms, R 2a and R 2b Each independently represents a hydrogen atom or a methyl group.

[0063] R 1 The number of carbon atoms in the R is 1 to 9. From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, R 1 The number of carbon atoms in R may be 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, or 8 or more. From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, R 1 The number of oxygen atoms in R may be 6 or less, 5 or less, 4 or less, 3 or less, or 2 or less. 1It can be a hydrocarbon group with oxygen atoms bonded at both ends, or it can be a "-OC n H 2n -O-" group (n = 1 to 9). From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the (meth)acrylic compound may contain R 1 Compounds without a ring structure may also include R 1 The (meth)acrylic compound may include R 2a and R 2b From the viewpoint of easily obtaining a low dielectric loss tangent in the cured product, the (meth)acrylic compound may contain R in the general formula (I): 2a and R 2b A compound wherein at least one of the radicals is a methyl group.

[0064] From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content of the compound represented by the general formula (I) may be 50% by mass or more, more than 50% by mass, 70% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, or more than 99% by mass, based on the total mass of the (meth)acrylic compound or the total mass of the methacrylic compound. The (meth)acrylic compound contained in the resin composition is substantially composed of the compound represented by the general formula (I) (based on the total mass of the (meth)acrylic compound contained in the resin composition, the content of the compound represented by the general formula (I) is substantially 100% by mass). The methacrylic compound contained in the resin composition is substantially composed of the compound represented by the general formula (I) (based on the total mass of the methacrylic compound contained in the resin composition, the content of the compound represented by the general formula (I) is substantially 100% by mass).

[0065] The (meth)acrylic compound may contain a (meth)acrylic compound having a hydroxyl group, or may not contain a (meth)acrylic compound having a hydroxyl group. The methacrylic compound may contain a methacrylic compound having a hydroxyl group, or may not contain a methacrylic compound having a hydroxyl group. Based on the total mass of the (meth)acrylic compound or the total mass of the methacrylic compound, the content of the (meth)acrylic compound having a hydroxyl group or the content of the methacrylic compound having a hydroxyl group may be 5% by mass or less, less than 5% by mass, 1% by mass or less, 0.1% by mass or less, 0.01% by mass or less, or substantially 0% by mass.

[0066] From the viewpoint of adjusting the tensile modulus of the cured product and the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the molecular weight of the (meth)acrylic compound or methacrylic compound may be within the following ranges. The molecular weight may be 80 or more, 100 or more, 120 or more, 150 or more, 180 or more, 200 or more, 220 or more, 250 or more, 260 or more, 280 or more, 290 or more, 300 or more, or 320 or more. The molecular weight may be 1000 or less, 800 or less, 600 or less, 550 or less, 500 or less, 450 or less, 400 or less, 350 or less, 320 or less, 300 or less, or 280 or less. From these viewpoints, the molecular weight may be 80-1000, 80-500, 80-400, 80-300, 100-1000, 100-500, 100-400, 100-300, 200-1000, 200-500, 200-400, 200-300, 250-1000, 250-500, 250-400, 250-300, 300-1000, 300-500 or 300-400.

[0067] As the content of the (meth) acrylic acid compound or the content of the methacrylic acid compound, from the viewpoint of easily obtaining a high tensile elastic modulus in the cured product and the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content B1 can be within the following ranges relative to 100 parts by mass of the polymer (polymer contained in the resin composition) or 100 parts by mass of the styrene block copolymer. The content B1 can be 1 part by mass or more, 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, or 25 parts by mass or more. The content B1 can be 300 parts by mass or less, 200 parts by mass or less, 100 parts by mass or less, 80 parts by mass or less, 60 parts by mass or less, 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, or 25 parts by mass or less. From these viewpoints, the content B1 may be 1 to 300 parts by mass, 10 to 300 parts by mass, 20 to 300 parts by mass, 1 to 100 parts by mass, 10 to 100 parts by mass, 20 to 100 parts by mass, 1 to 50 parts by mass, 10 to 50 parts by mass or 20 to 50 parts by mass.

[0068] As the content of the (meth)acrylic compound or the content of the methacrylic compound, from the viewpoint of easily obtaining a high tensile modulus in the cured product and from the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content B2 can be within the following range based on the total mass of the resin composition (excluding the mass of the organic solvent), the polymer (polymer contained in the resin composition), the total amount of the (meth)acrylic compound and the polymerization initiator, the total amount of the polymer (polymer contained in the resin composition), the methacrylic compound and the polymerization initiator, the total amount of the styrene block copolymer, the (meth)acrylic compound and the polymerization initiator, the total amount of the styrene block copolymer, the methacrylic compound and the polymerization initiator, the total amount of the polymer (polymer contained in the resin composition) and the (meth)acrylic compound, the total amount of the polymer (polymer contained in the resin composition) and the methacrylic compound, the total amount of the styrene block copolymer and the (meth)acrylic compound, or the total amount of the styrene block copolymer and the methacrylic compound. The content B2 may be 1% by mass or more, 5% by mass or more, 10% by mass or more, 15% by mass or more, 18% by mass or more, or 20% by mass or more. The content B2 may be 80% by mass or less, less than 80% by mass, 70% by mass or less, less than 70% by mass, 60% by mass or less, less than 60% by mass, 50% by mass or less, less than 50% by mass, 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, or 20% by mass or less. From these viewpoints, the content B2 may be 1 to 80% by mass, 1 to 50% by mass, 1 to 30% by mass, 10 to 80% by mass, 10 to 50% by mass, 10 to 30% by mass, 15 to 80% by mass, 15 to 50% by mass, or 15 to 30% by mass.

[0069] The resin composition involved in the present embodiment contains a polymerization initiator. As a polymerization initiator, there is no particular limitation as long as it is a compound that initiates polymerization by heating, irradiation with active light (ultraviolet rays, etc.), but for example, a thermal polymerization initiator and a photopolymerization initiator (except a compound corresponding to the thermal polymerization initiator) can be cited.

[0070] Examples of the thermal polymerization initiator include ketone peroxides such as methyl ethyl ketone peroxide, cyclohexanone peroxide, and methylcyclohexanone peroxide; peroxyketals such as 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-2-methylcyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, and 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane; hydroperoxides such as p-menthane hydroperoxide; α,α'-bis(tert-butylperoxy)diisopropylbenzene, diisopropylbenzene peroxide, tert-butylisopropylbenzene peroxide, di-tert-butylisopropylbenzene peroxide, and di-tert-butylisopropylbenzene peroxide. peroxides, such as dialkyl peroxides; diacyl peroxides such as octanoyl peroxide, lauroyl peroxide, stearyl peroxide, and benzoyl peroxide; peroxy carbonates such as bis(4-tert-butylcyclohexyl)peroxydicarbonate, di-2-ethoxyethyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, and di-3-methoxybutyl peroxycarbonate; tert-butyl peroxypivalate, tert-hexyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 2,5-dimethyl-2,5-bis(2-ethylhexanoyl peroxy)hexane, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy- 2-ethylhexanoate, tert-butyl peroxyisobutyrate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxybenzoate, tert-hexyl peroxybenzoate, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, tert-butyl peroxyacetate and other peroxyesters; phthalic anhydride, maleic anhydride, trimellitic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyl nadic anhydride, nadic anhydride, glutaric anhydride, dimethyl glutaric anhydride, diethyl glutaric anhydride, Acid anhydrides such as succinic anhydride, methylhexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, 4,4'-diphthalic anhydride, 4,4'-carbonyldiphthalic anhydride, 4,4'-sulfonyldiphthalic anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 4,4'-oxydiphthalic anhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, and 2,3,6,7-naphthalenetetracarboxylic anhydride; azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2'-dimethylvaleronitrile); etc.

[0071] Examples of the photopolymerization initiator include acylphosphine oxide compounds, acetophenone compounds, anthraquinone compounds, benzophenone compounds, imidazole compounds, acridine compounds, and oxime ester compounds.

[0072] From the viewpoint of easily obtaining a high tensile modulus of elasticity in a cured product and from the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in a cured product, the polymerization initiator may include a thermal polymerization initiator, a thermal free radical polymerization initiator, or a thermal cationic polymerization initiator. From the viewpoint of easily obtaining a high tensile modulus of elasticity in a cured product and from the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in a cured product, the polymerization initiator may include a peroxide, a peroxyester, or 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane.

[0073] The content of the polymerization initiator may be within the following ranges based on the total mass of the resin composition (excluding the mass of the organic solvent), the total amount of the polymer (the polymer contained in the resin composition), the (meth)acrylic compound and the polymerization initiator, the total amount of the polymer (the polymer contained in the resin composition), the methacrylic compound and the polymerization initiator, the total amount of the styrene block copolymer, the (meth)acrylic compound and the polymerization initiator, the total amount of the styrene block copolymer, the methacrylic compound and the polymerization initiator, the total amount of the polymer (the polymer contained in the resin composition) and the (meth)acrylic compound, the total amount of the polymer (the polymer contained in the resin composition) and the methacrylic compound, the total amount of the styrene block copolymer and the (meth)acrylic compound, or the total amount of the styrene block copolymer and the methacrylic compound. From the viewpoint of easily obtaining a high tensile modulus of elasticity in a cured product, from the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in a cured product, and from the viewpoint of easily obtaining excellent curability, the content of the polymerization initiator can be 0.01% by mass or more, 0.05% by mass or more, 0.1% by mass or more, more than 0.1% by mass, 0.3% by mass or more, 0.5% by mass or more, 0.8% by mass or more, 0.9% by mass or more, or 1% by mass or more. From the viewpoint of easily obtaining a high tensile modulus of elasticity in a cured product, and from the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in a cured product, the content of the polymerization initiator can be 10% by mass or less, 8% by mass or less, 5% by mass or less, 3% by mass or less, 2% by mass or less, less than 2% by mass, 1.5% by mass or less, or 1% by mass or less. From these viewpoints, the content of the polymerization initiator may be 0.01 to 10 mass %, 0.01 to 5 mass %, 0.01 to 2 mass %, 0.1 to 10 mass %, 0.1 to 5 mass %, 0.1 to 2 mass %, 0.5 to 10 mass %, 0.5 to 5 mass % or 0.5 to 2 mass %.

[0074] The resin composition involved in the present embodiment may contain additives other than styrene block copolymers, (meth) acrylic acid compounds and polymerization initiators. As such additives, polymers (except compounds corresponding to styrene block copolymers), polymerizable compounds (except compounds corresponding to (meth) acrylic acid compounds), curing accelerators, antioxidants, ultraviolet absorbers, visible light absorbers, colorants, plasticizers, stabilizers, fillers (fillers), reducing agents, bicarbonates, etc. can be cited. As polymerizable compounds, halogenated vinylidene compounds, vinyl ether compounds, vinyl ester compounds, vinyl amide compounds, aromatic vinyl compounds (such as vinyl pyridine compounds), allyl compounds, epoxy compounds, etc. can be cited. As reducing agents, vanadium acetylacetonate, vanadium acetylacetonate, cobalt acetylacetonate, copper acetylacetonate, vanadium cyclohexaneate, vanadium stearate, copper cyclohexaneate, copper acetate, cobalt octoate, etc. can be cited.

[0075] The content of the filler may be 100% by mass or less, less than 100% by mass, 50% by mass or less, 20% by mass or less, less than 20% by mass, 10% by mass or less, 1% by mass or less, 0.1% by mass or less, or substantially 0% by mass, based on the total amount of the polymer (polymer contained in the resin composition) and the (meth)acrylic compound, the total amount of the polymer (polymer contained in the resin composition) and the methacrylic compound, the total amount of the styrene block copolymer and the (meth)acrylic compound, or the total amount of the styrene block copolymer and the methacrylic compound. The content of the reducing agent may be 0.01 parts by mass or less, less than 0.01 parts by mass, 0.001 parts by mass or substantially 0 parts by mass, based on 100 parts by mass of the (meth)acrylic compound or 100 parts by mass of the methacrylic compound. The content of the bicarbonate may be 0.1 parts by mass or less, less than 0.1 parts by mass, 0.01 parts by mass or less, 0.001 parts by mass or less, or substantially 0 parts by mass, based on 100 parts by mass of the (meth)acrylic compound or 100 parts by mass of the methacrylic compound.

[0076] The resin composition involved in this embodiment may contain an organic solvent. The resin composition involved in this embodiment can be used as a resin varnish by diluting with an organic solvent. As an organic solvent, aromatic hydrocarbons such as toluene, xylene, mesitylene, isopropylbenzene, and p-isopropylbenzene can be cited; cyclic ethers such as tetrahydrofuran and 1,4-dioxane; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and 4-hydroxy-4-methyl-2-pentanone; esters such as methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, and γ-butyrolactone; carbonates such as ethylene carbonate and propylene carbonate; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0077] The total light transmittance per 100 μm thickness of the layer containing the resin composition involved in the present embodiment or the cured product involved in the present embodiment can be 90% or more or 91% or more. The total light transmittance can be measured according to the method specified in JIS K 7136, for example, using NDH-5000 (product name) manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd. The total light transmittance described below can also be measured using the same method.

[0078] The laminated body according to the present embodiment includes a base film (support film) and a transparent resin layer disposed on the base film, and the transparent resin layer includes at least one selected from the group consisting of the resin composition according to the present embodiment and a cured product thereof.

[0079] As the constituent material of the substrate film, polyester (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, etc.), polyolefin (polyethylene, polypropylene, cycloolefin polymer, etc.), polycarbonate, polyamide, polyimide, polyamideimide, polyetherimide, polyether sulfide, polyether sulfone, polyether ketone, polyphenylene ether, polyphenylene sulfide, etc. can be mentioned. The thickness of the substrate film can be 1 to 200 μm, 10 to 100 μm, 20 to 80 μm or 20 to 50 μm.

[0080] From the viewpoint of easily obtaining excellent transmittance and easily thinning the transparent antenna, the thickness of the transparent resin layer can be 1000 μm or less, 800 μm or less, 500 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 80 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 15 μm or less, 12 μm or less, 10 μm or less, 9 μm or less or 8 μm or less. From the perspective of reducing transmission loss and facilitating improving antenna characteristics, the thickness of the transparent resin layer can be greater than 0.1 μm, greater than 0.5 μm, greater than 0.75 μm, greater than 1 μm, greater than 2 μm, greater than 3 μm, greater than 5 μm, greater than 6 μm, greater than 7 μm, greater than 8 μm, greater than 10 μm, greater than 20 μm, greater than 30 μm, greater than 40 μm, greater than 50 μm, greater than 80 μm or greater than 100 μm. From these viewpoints, the thickness of the transparent resin layer can be 0.1 to 1000 μm, 1 to 1000 μm, 10 to 500 μm, 20 to 200 μm, 50 to 200 μm, 0.1 to 500 μm, 0.1 to 100 μm, 0.5 to 250 μm, 0.5 to 150 μm, 0.75 to 100 μm, 1 to 50 μm, 2 to 30 μm, 3 to 20 μm or 5 to 20 μm.

[0081] A first aspect of the laminated body according to the present embodiment may include a protective film disposed on the transparent resin layer. A second aspect of the laminated body according to the present embodiment may include a conductive member disposed on the transparent resin layer.

[0082] As the constituent material of the protective film, the constituent materials mentioned above as the constituent material of the base film can be used. The protective film can be the same film as the base film or a film different from the base film. The thickness of the protective film can be 1 to 200 μm, 10 to 100 μm, 20 to 80 μm or 20 to 50 μm.

[0083] The conductive component may be solid or may have a patterned portion (may be patterned). In a conductive component having a patterned portion (hereinafter referred to as a "patterned conductive component"), a portion or all of the conductive component may be patterned (the same also applies to the following description related to the case where the conductive component has a patterned portion). Examples of the shape of the patterned portion include a mesh shape, a spiral shape, and the like. In the case of using a transparent antenna having a solid conductive component, the conductive component may be patterned (e.g., mesh processing). The patterned (e.g., mesh) conductive component may be composed of wires (e.g., metal wires). Examples of the constituent materials of the conductive component include metal materials, carbon materials (e.g., graphene), conductive polymers, and the like. Examples of metal materials include copper, silver, gold, and the like. From the viewpoint of easily obtaining excellent conductivity and easily reducing manufacturing costs, the conductive component may contain copper.

[0084] The conductive component can be a single layer or a multilayer. The multilayer conductive component can, for example, have a first conductive component (e.g., a metal component) disposed on a transparent resin layer, and a second conductive component (e.g., a metal component) disposed on the first conductive component. At least one selected from the group consisting of the first conductive component and the second conductive component can be solid, or it can have a patterned (e.g., mesh) portion. The second conductive component can be used as a protective layer to suppress contamination, damage, etc. of the first conductive component, thereby also being able to improve the operability of the laminate. At least one selected from the group consisting of the first conductive component and the second conductive component can contain copper.

[0085] The thickness of the conductive component (the total thickness in the case where the conductive component is multi-layered), the thickness of the first conductive component or the thickness of the second conductive component can be within the following range. From the perspective that the conductive component is not easily damaged and that a solid conductive component is easily patterned (e.g., mesh processing), the thickness can be 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 18 μm or less, 15 μm or less, 10 μm or less, 8 μm or less, 5 μm or less, 3 μm or less or 2 μm or less. From the perspective of easily obtaining excellent elongation, the thickness can be 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, 0.8 μm or more, 1 μm or more, 1.2 μm or more, 1.5 μm or more or 2 μm or more. From these viewpoints, the thickness may be 0.1 to 50 μm, 0.1 to 30 μm, 0.1 to 20 μm, 0.1 to 10 μm, 0.5 to 5 μm or 1 to 3 μm.

[0086] The thickness of the first conductive component may be smaller than the thickness of the second conductive component. In the case where the conductive component is multi-layered, the thickness (total thickness) of the conductive component or the thickness of the second conductive component may be greater than 3 μm, greater than 5 μm, greater than 8 μm, greater than 10 μm, greater than 15 μm, greater than 18 μm or greater than 20 μm.

[0087] The laminated body involved in the second embodiment may include a protective film disposed on the conductive component. As the protective film, the protective film described above can be used as the protective film in the laminated body involved in the first embodiment. A demoulding treatment may be applied to at least a portion of one side of the conductive component side in the protective film, or a peeling layer may be configured on at least a portion of one side of the conductive component side in the protective film. For example, the laminated body involved in the second embodiment may include a substrate film, a transparent resin layer, a conductive component and a protective film, the conductive component is a single layer, and a demoulding treatment is applied to at least a portion of one side of the conductive component side in the protective film.

[0088] In the laminated body involved in the second embodiment, as a layer comprising at least one selected from the group consisting of a photosensitive composition and a cured product thereof, a layer L disposed on a conductive component may be provided. The photosensitive composition has photosensitivity to active light (ultraviolet rays, etc.), and may have positive photosensitivity or negative photosensitivity. The photosensitive composition may have photocurability that is cured by light irradiation. Layer L may be either before or after light irradiation, or may have at least one selected from the group consisting of an uncured portion and a cured portion. Layer L may be either before or after light irradiation, or may have at least one selected from the group consisting of an unexposed portion and an exposed portion. The constituent material of the photosensitive composition is not particularly limited.

[0089] Figure 1 and Figure 2 It is a schematic cross-sectional view showing an example of a laminated body. Figure 1 The laminate 10 of (a) includes a base film 10a, a transparent resin layer 10b disposed on the base film 10a, and a protective film 10c disposed on the transparent resin layer 10b. The transparent resin layer 10b is formed of the resin composition according to the present embodiment or the cured product according to the present embodiment. Figure 1 The laminate 20 of (b) includes a base film 20a, a transparent resin layer 20b disposed on the base film 20a, and a conductive member 20c disposed on the transparent resin layer 20b. The transparent resin layer 20b is formed of the resin composition according to the present embodiment or the cured product according to the present embodiment. Figure 2 The laminate 30 includes a substrate film 30a, a transparent resin layer 30b disposed on the substrate film 30a, a conductive member 30c disposed on the transparent resin layer 30b, and a conductive member 30d disposed on the conductive member 30c. The transparent resin layer 30b is formed of the resin composition involved in this embodiment or the cured product involved in this embodiment.

[0090] The resin composition and cured product thereof according to the present embodiment can be used in a transparent antenna and a method for manufacturing the same. In a transparent antenna, the applicable part of the resin composition and cured product thereof according to the present embodiment is not particularly limited. Regarding the case of using the resin composition according to the present embodiment, hereinafter, the substrate obtained by curing the resin composition of the transparent resin layer in the curing process is referred to as a "transparent substrate", and the layer that can contain the state before curing the resin composition of the transparent resin layer in the curing process is referred to as a "transparent resin layer".

[0091] The first mode of the transparent antenna involved in the present embodiment comprises a transparent substrate and a conductive component arranged on the transparent substrate, and the transparent substrate comprises a cured product of the resin composition involved in the present embodiment. The transparent antenna involved in the first mode may comprise a covering component arranged on the conductive component, and the covering component may comprise a cured product of the resin composition involved in the present embodiment, or may not comprise a cured product of the resin composition involved in the present embodiment (or may comprise a cured product of a resin composition that does not correspond to the resin composition involved in the present embodiment). The second mode of the transparent antenna involved in the present embodiment comprises a conductive component and a covering component arranged on the conductive component, and the covering component comprises a cured product of the resin composition involved in the present embodiment. The second mode of the transparent antenna involved in the present embodiment may comprise a transparent substrate, and the conductive component may be arranged on the transparent substrate. In the transparent antenna involved in the second mode, the transparent substrate may comprise a cured product of the resin composition involved in the present embodiment, or may not comprise a cured product of the resin composition involved in the present embodiment (or may comprise a cured product of a resin composition that does not correspond to the resin composition involved in the present embodiment). The transparent antenna according to the present embodiment may include a transparent substrate, a conductive member disposed on the transparent substrate, and a covering member disposed on the conductive member, wherein at least one selected from the group consisting of the transparent substrate and the covering member includes a cured product of the resin composition according to the present embodiment.

[0092] In the transparent antenna involved in this embodiment, the covering component can be arranged on at least a part (a part or all) of the conductive component. The covering component can be arranged on at least a part (a part or all) of the transparent substrate. In addition to the part arranged on the conductive component, the covering component can also have a part arranged on the transparent substrate but not arranged on the conductive component. The conductive component is arranged on a part of the transparent substrate (for example, a part of the main surface of the transparent substrate), so that the covering component (transparent component) can be arranged on the transparent substrate and the conductive component. The covering component can protect the conductive component by covering the conductive component. The covering component can protect the transparent substrate by covering the transparent substrate.

[0093] The covering member may abut against the conductive member. The covering member may abut against the transparent substrate or may not abut against the transparent substrate. The transparent substrate may abut against a transparent member different from the covering member (for example, a supporting member described later). The covering member may abut against a transparent member different from the transparent substrate (for example, a protective member described later).

[0094] In the transparent antenna involved in the present embodiment, at least one component selected from the group consisting of a transparent substrate and a covering component can contain a cured product of the resin composition involved in the present embodiment. In the case where one of the transparent substrate and the covering component (hereinafter referred to as "component A") does not contain a cured product of the resin composition involved in the present embodiment, component A can be formed of a material having a total light transmittance of 90% or more or 91% or more per 100 μm thickness. As the constituent material of component A, polyolefins (polyethylene, polypropylene, cycloolefin polymer (COP), etc.), polyesters (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, etc.), polycarbonate, polyamide, polyimide, polyamideimide, polyetherimide, polyether sulfide, polyether sulfone, polyether ketone, polyphenylene ether, polyphenylene sulfide, etc. can be cited. For example, component A can contain a cycloolefin polymer.

[0095] In the transparent antenna involved in this embodiment, as the structure of the conductive component, the above-mentioned structure can be used for the conductive component in the laminated body involved in the second embodiment. For example, the conductive component can contain copper. The conductive component can be solid or have a patterned (e.g., mesh) portion. The conductive component can be a single layer. As the thickness of the transparent substrate, the above-mentioned thickness can be used for the transparent resin layer of the laminated body involved in this embodiment.

[0096] The transparent antenna involved in this embodiment may include a supporting member supporting a transparent substrate, that is, it may include a supporting member, a transparent substrate arranged on the supporting member, and a conductive member arranged on the transparent substrate. The transparent antenna involved in this embodiment may include a protective member arranged on a covering member, that is, it may include a transparent substrate, a conductive member arranged on the transparent substrate, a covering member arranged on the conductive member, and a protective member arranged on the covering member.

[0097] The shapes of the supporting member and the protective member are not particularly limited, and may be film-shaped, substrate-shaped, indefinitely shaped, etc. As constituent materials of the supporting member and the protective member, resin materials, inorganic materials, etc. may be cited. As resin materials, polyolefins (polyethylene, polypropylene, cycloolefin polymers, etc.), polyesters (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, etc.), polycarbonates, polyamides, polyimides, polyamide-imides, polyetherimides, polyether sulfides, polyether sulfones, polyether ketones, polyphenylene ethers, polyphenylene sulfides, etc. may be cited. As inorganic materials, glass, etc. may be cited. The supporting member and the protective member are not limited to being transparent, and may be transparent members (transparent films, transparent substrates, etc.) or opaque members. The supporting member and the protective member may be formed of a material having a total light transmittance of more than 90% per a thickness of 100 μm. From the viewpoint of low dielectric, the supporting member may contain polyolefins.

[0098] In the first mode of the method for manufacturing the transparent antenna involved in the present embodiment, as a method for obtaining the transparent antenna involved in the first mode, a processing step of patterning (e.g., processing into a mesh) at least a portion of a conductive component (solid conductive component) disposed on a transparent resin layer comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product. In the processing step, a patterned (e.g., mesh-like) conductive component can be obtained by etching the conductive component in a state where a patterned resist layer is disposed on the conductive component of a laminate having a transparent resin layer and a conductive component disposed on the transparent resin layer. The resist layer can be removed after etching the conductive component. The patterned resist layer can be obtained by removing the uncured portion or the cured portion of the photosensitive layer (a layer comprising a photosensitive composition) disposed on the conductive component. For example, the patterned resist layer can be obtained by irradiating (exposing) a photosensitive layer (a layer containing a photosensitive composition) disposed on a conductive member with active light (e.g., ultraviolet rays), and then removing (developing) the unexposed portion (when the photosensitive layer has negative photosensitivity) or the exposed portion (when the photosensitive layer has positive photosensitivity). As the photosensitive layer, the above-mentioned layer L can be used.

[0099] The laminated body having the conductive member disposed on the transparent resin layer can be obtained by forming the conductive member on the transparent resin layer comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and the cured product thereof, for example, after removing the protective film of the laminated body involved in the first embodiment, the conductive member can be formed on the transparent resin layer. The laminated body having the conductive member disposed on the transparent resin layer can be the laminated body involved in the second embodiment.

[0100] The manufacturing method of the transparent antenna involved in the first embodiment may include a curing process of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before, after, or before and after the processing process. In the curing process, the uncured resin composition can be irradiated with active light to cure the resin composition, or the uncured resin composition can be heated to cure the resin composition. As active light, there is no particular limitation, but ultraviolet rays can be used, and ultraviolet rays with a wavelength of 365nm can also be used. The active light can be irradiated to the resin composition through a light-transmitting film (for example, a substrate film or a protective film of the laminated body involved in this embodiment). The curing process in another embodiment of the manufacturing method of the transparent antenna described below can be the same as the curing process in the manufacturing method of the transparent antenna involved in the first embodiment.

[0101] In the second mode of the method for manufacturing the transparent antenna involved in the present embodiment, as a method for obtaining the transparent antenna involved in the first mode, a formation process of forming a patterned (e.g., mesh-shaped) conductive component is formed in a state where a patterned resist layer is arranged on a transparent resin layer comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product. In the formation process, the resist layer can be used as a mask, and a patterned (e.g., mesh-shaped) conductive component can be formed by plating or sputtering. The resist layer can be removed after the formation process. The method for manufacturing the transparent antenna involved in the second mode may include a curing process of curing the transparent resin layer (resin composition of the transparent resin layer) before the formation process, after the formation process, or before and after the formation process to obtain a cured product (transparent substrate).

[0102] The third mode of the method for manufacturing the transparent antenna involved in the present embodiment includes a removal step of removing the substrate film in the laminate involved in the second mode. The conductive component in the laminate involved in the second mode may have a patterned (e.g., mesh-like) portion. In the case where the transparent resin layer of the laminate during the removal step contains a cured product (in the case where the transparent resin layer is a transparent substrate), a laminate of a transparent substrate and a conductive component (a patterned (e.g., mesh-like) conductive component, etc.) can be obtained as a transparent antenna through the removal step. The method for manufacturing the transparent antenna involved in the third mode may include a curing step of curing the transparent resin layer (the resin composition of the transparent resin layer) before the removal step, after the removal step, or before and after the removal step to obtain a cured product (transparent substrate).

[0103] The fourth mode of the method for manufacturing the transparent antenna involved in the present embodiment includes a lamination step of laminating the transparent resin layer in the laminated body involved in the present embodiment on a supporting member. As the supporting member, the above-mentioned supporting member can be used for the transparent antenna. In the lamination step, the transparent resin layer can be laminated on the supporting member in a state where the base film in the laminated body involved in the present embodiment is removed, or the transparent resin layer can be laminated on the supporting member in a state where the protective film in the laminated body involved in the first mode is removed. The method for manufacturing the transparent antenna involved in the fourth mode may include a removal step A of removing the base film in the laminated body involved in the present embodiment, and may also include a removal step B of removing the protective film in the laminated body involved in the first mode.

[0104] In the case of using the laminated body involved in the second embodiment, in the lamination process, the transparent resin layer and the conductive component can be laminated on the supporting component in a state where the transparent resin layer is located closer to the supporting component than the conductive component, or the transparent resin layer and the conductive component can be laminated on the supporting component in a state where the transparent resin layer is in contact with the supporting component. In the lamination process, the conductive component can be solid or have a patterned (e.g., mesh) portion. In the lamination process, the transparent resin layer and the conductive component can be laminated on the supporting component in a state where the base film in the laminated body involved in the second embodiment is removed. In the case where the laminated body involved in the second embodiment has a protective film disposed on the conductive component, in the lamination process, the transparent resin layer, the conductive component and the protective film can be laminated on the supporting component in a state where the transparent resin layer is located closer to the supporting component than the conductive component (the conductive component is located closer to the transparent resin layer than the protective film). When the laminated body according to the second embodiment includes a base film, a transparent resin layer, a conductive member, and a protective film, the method for manufacturing a transparent antenna according to the fourth embodiment may include a removal step B of removing the protective film after the removal step A and the lamination step. When the laminated body according to the second embodiment includes the above-mentioned layer L, in the lamination step, the transparent resin layer, the conductive member, and the layer L may be laminated on the support member in a state where the transparent resin layer is located closer to the support member than the conductive member.

[0105] In the case where the supporting member and the conductive member are stacked with good adhesion in a laminate having a supporting member and a conductive member arranged on the supporting member, surface treatment (plasma treatment, corona treatment, etc.) is sometimes applied to the supporting member, and the manufacturing process of the laminate may become complicated. For example, when polyolefin is used as the constituent material of the supporting member, since the adhesion between polyolefin and the conductive member (for example, metal materials such as copper) is low, surface treatment is sometimes required to obtain sufficient adhesion. On the other hand, according to the manufacturing method of the transparent antenna involved in the fourth embodiment, sufficient adhesion between the supporting member and the conductive member is obtained through the transparent substrate, and at the same time, a laminate of the supporting member and the conductive member (a laminate having a supporting member, a transparent substrate and a conductive member) can be obtained as a transparent antenna. For example, sufficient adhesion between the supporting member containing polyolefin and the conductive member containing copper can be obtained through the transparent substrate, and at the same time, a transparent antenna can be obtained. Furthermore, according to the manufacturing method of the transparent antenna involved in the fourth embodiment, by laminating the laminated body involved in the second embodiment on the supporting member, the transparent resin layer and the conductive member can be supplied to the supporting member together, and each component does not need to be formed on the supporting member each time the transparent antenna is manufactured, and the transparent antenna can be obtained by a simple method. In the case where the laminated body involved in the second embodiment has the above-mentioned layer L, according to the manufacturing method of the transparent antenna involved in the fourth embodiment, by laminating the laminated body involved in the second embodiment on the supporting member, the transparent resin layer, the conductive member and the layer L can be supplied to the supporting member together, and each component does not need to be formed on the supporting member each time the transparent antenna is manufactured, and the transparent antenna can be obtained by a simple method. In addition, according to the manufacturing method of the transparent antenna involved in the fourth embodiment, as the constituent material of the transparent resin layer or the transparent substrate, by using a material having excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.), a transparent antenna having excellent antenna characteristics can be obtained.

[0106] In the method for manufacturing a transparent antenna according to the fourth aspect, the transparent resin layer in the removal step A, the removal step B, and the lamination step may be uncured or may be a cured product. The method for manufacturing a transparent antenna according to the fourth aspect may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the removal step A, before the removal step B, before the lamination step, after the removal step A, after the removal step B, after the lamination step, before and after the removal step A, before and after the removal step B, or before and after the lamination step.

[0107] In the method for manufacturing a transparent antenna according to the fourth embodiment, the conductive component in the removal step A, the removal step B, and the stacking step may be solid or may have a patterned (e.g., mesh-like) portion. When the conductive component is solid, the method for manufacturing a transparent antenna according to the fourth embodiment may include a processing step A of patterning at least a portion of the conductive component (e.g., processing into a mesh) after the stacking step. In the processing step A, a patterned resist layer may be used as a mask to pattern at least a portion of the conductive component by etching at least a portion of the conductive component. The method in which the conductive component has a patterned portion in the stacking step may be as follows: the method for manufacturing a transparent antenna according to the fourth embodiment includes a stacking step in which the transparent resin layer in a stack having a transparent resin layer and a conductive component disposed on the transparent resin layer is located on a side closer to the supporting component than the conductive component, the transparent resin layer comprises at least one selected from the group consisting of the resin composition and its cured product according to the present embodiment, and the conductive component has a patterned portion.

[0108] When the laminated body according to the second embodiment includes the layer L, the method for producing a transparent antenna according to the fourth embodiment may include a processing step B of obtaining a patterned layer L (resist layer) by patterning at least a portion of the layer L after the lamination step and before the processing step A. In the processing step B, at least a portion of the layer L can be patterned by removing (developing) an unexposed portion (when the layer L has negative photosensitivity) or an exposed portion (when the layer L has positive photosensitivity), and after exposing the layer L, the unexposed portion or the exposed portion is removed (developed), thereby patterning at least a portion of the layer L. The method for producing a transparent antenna according to the fourth embodiment may include a step of exposing at least a portion of the layer L before the lamination step. As an embodiment using a laminate having a layer comprising at least one selected from the group consisting of a photosensitive composition and a cured product thereof, the following embodiment may be used: the method for manufacturing a transparent antenna involved in the fourth embodiment includes a lamination step of laminating the laminate on a supporting member in a state in which the first layer in the laminate having a first layer, a second layer, and a conductive member arranged between the first layer and the second layer is located closer to the supporting member than the second layer, the first layer comprises at least one selected from the group consisting of the resin composition involved in this embodiment and a cured product thereof, and the second layer comprises at least one selected from the group consisting of a photosensitive composition and a cured product thereof.

[0109] In the method for manufacturing a transparent antenna according to the fourth embodiment, the conductive component in the removal step A, the removal step B, and the lamination step may be a multilayer, or may include a first conductive component disposed on a transparent resin layer, and a second conductive component disposed on the first conductive component. At least one selected from the group consisting of the first conductive component and the second conductive component may be solid, or may include a patterned (e.g., mesh-like) portion. At least one selected from the group consisting of the first conductive component and the second conductive component may contain copper. When the conductive component includes the first conductive component and the second conductive component, in the lamination step, the transparent resin layer and the conductive component may be laminated on the supporting component in a state where the first conductive component is located closer to the supporting component than the second conductive component. The method for manufacturing a transparent antenna according to the fourth embodiment may include a removal step C of removing the second conductive component after the lamination step. In the removal step C, the second conductive component can be peeled off from the first conductive component. The method for manufacturing a transparent antenna according to the fourth embodiment may include a processing step of patterning (e.g., processing into a mesh) at least a portion of the first conductive component after the removal step C. In the processing step, for example, the first conductive member may be etched while a patterned resist layer is disposed on the first conductive member. The method for manufacturing a transparent antenna according to the fourth aspect may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the removal step C, after the removal step C, or before and after the removal step C.

[0110] In the fifth aspect of the method for manufacturing a transparent antenna involved in the present embodiment, as a method for obtaining the transparent antenna involved in the first aspect, it is a method for manufacturing a transparent antenna using a laminate (the laminate involved in the second aspect) comprising the above-mentioned substrate film, the above-mentioned transparent resin layer (including at least one transparent resin layer selected from the group consisting of the resin composition involved in the present embodiment and its cured product), and the above-mentioned conductive component having a first conductive component and a second conductive component, and the manufacturing method comprises a removal step C of removing the second conductive component in a state where the transparent resin layer and the conductive component are stacked on the supporting component while the transparent resin layer in the laminate involved in the second aspect is located on the supporting component side relative to the conductive component.

[0111] The manufacturing method of the transparent antenna involved in the fifth embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) in a state where the transparent resin layer and the conductive component are stacked on the supporting component before the removal step C, after the removal step C, or before and after the removal step C. In the curing step, the transparent resin layer may be cured in a state where the transparent resin layer and the conductive component are stacked on the supporting component while the transparent resin layer is located closer to the supporting component than the conductive component. The manufacturing method of the transparent antenna involved in the fifth embodiment may include a processing step of patterning (for example, processing into a mesh shape) at least a portion of the first conductive component after removing the second conductive component (after the removal step C). An example of a method for manufacturing a transparent antenna according to the fifth embodiment is a method for manufacturing a laminated body including the substrate film, the transparent resin layer (uncured transparent resin layer), and the conductive member having the first conductive member and the second conductive member as the laminated body according to the second embodiment, the manufacturing method comprising the removal step A (first removal step), a lamination step, a curing step, and a removal step C (second removal step). In the method for manufacturing a transparent antenna according to the fifth embodiment, at least one selected from the group consisting of the first conductive member and the second conductive member may contain copper. Furthermore, the first conductive member in the laminated body may be solid or may have a patterned (e.g., meshed) portion.

[0112] In the sixth aspect of the method for manufacturing a transparent antenna according to the present embodiment, as a method for obtaining the transparent antenna according to the first aspect, a removal step B is included in which a transparent resin layer (including at least one transparent resin layer selected from the group consisting of the resin composition according to the present embodiment and its cured product), a conductive component and a protective film are sequentially stacked on a supporting component to remove the protective film. In this case, the laminate may be, for example, a single-layer conductive component, and a demolding treatment is applied to at least a portion of one surface of the conductive component side of the protective film. The method for manufacturing a transparent antenna according to the sixth aspect may include: a removal step A of removing the substrate film in the laminate according to the second aspect before the removal step B; and a stacking step of stacking the transparent resin layer, the conductive component and the protective film on the supporting component. The method for manufacturing a transparent antenna according to the sixth aspect may include a curing step of curing the transparent resin layer (the resin composition of the transparent resin layer) before the removal step B, after the removal step B, or before and after the removal step B to obtain a cured product (transparent substrate).

[0113] The manufacturing method of the transparent antenna involved in the 1st to 6th embodiments may include a covering component forming step of forming a covering component (excluding the covering component of the resin composition and its cured product involved in this embodiment) on a conductive component, and may also include a step of configuring a protective component (such as a transparent component) on the covering component after the covering component forming step.

[0114] In the seventh aspect of the method for manufacturing the transparent antenna according to the present embodiment, as a method for obtaining the transparent antenna according to the second aspect, a covering component forming step is included in which a covering component including at least one selected from the group consisting of the resin composition according to the present embodiment and a cured product thereof is formed on a conductive component. In the covering component forming step, the covering component can be formed by supplying the resin composition according to the present embodiment to the conductive component, or the covering component (transparent resin layer) can be formed by disposing the transparent resin layer of the laminate according to the present embodiment on the conductive component. When the laminate according to the present embodiment is used, the transparent resin layer of the laminate according to the present embodiment can be disposed on the conductive component after removing the substrate film or the protective film. The step of forming a coating component can be a step of forming a coating component comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product on a conductive component in a stack comprising a transparent resin layer (a transparent resin layer supporting a conductive component) and a conductive component arranged on the transparent resin layer. It can also be a step of forming a coating component comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product on a transparent resin layer and a conductive component in a stack comprising a transparent resin layer (a transparent resin layer supporting a conductive component) and a conductive component arranged on a part of the transparent resin layer (for example, a part of the main surface of the transparent resin layer).

[0115] The manufacturing method of the transparent antenna involved in the 7th embodiment may include a curing step of curing the covering component (resin composition of the covering component) to obtain a cured product before the covering component forming step, after the covering component forming step, or before and after the covering component forming step. The manufacturing method of the transparent antenna involved in the 7th embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) supporting the conductive component to obtain a cured product (transparent substrate) before the covering component forming step, after the covering component forming step, or before and after the covering component forming step. The covering component and the transparent resin layer supporting the conductive component may be cured in the same curing step. The manufacturing method of the transparent antenna involved in the 7th embodiment may include a step of disposing a protective component (e.g., a transparent component) on the covering component after the covering component forming step.

[0116] In an eighth aspect of the method for manufacturing a transparent antenna according to the present embodiment, as a method for obtaining the transparent antenna according to the second aspect, a lamination step is included in which a laminate having a conductive component and a covering component disposed on the conductive component is laminated on a transparent resin layer in a state where the conductive component in the laminate having a conductive component and a covering component disposed on the conductive component is located closer to the transparent resin layer than the covering component, and the covering component comprises at least one selected from the group consisting of the resin composition according to the present embodiment and a cured product thereof. As the laminate having a conductive component and a covering component disposed on the conductive component, the laminate according to the second aspect can be used, and in the lamination step, the transparent resin layer in the laminate according to the second aspect can be disposed as the covering component.

[0117] The manufacturing method of the transparent antenna involved in the 8th embodiment may include a curing step of curing the covering member (resin composition of the covering member) to obtain a cured product before the lamination process, after the lamination process, or before and after the lamination process. The manufacturing method of the transparent antenna involved in the 8th embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the lamination process, after the lamination process, or before and after the lamination process. The covering member and the transparent resin layer may be cured in the same curing step. The manufacturing method of the transparent antenna involved in the 8th embodiment may include a step of configuring a protective member (such as a transparent member) on the covering member before the lamination process, after the lamination process, or before and after the lamination process.

[0118] In the manufacturing method of the transparent antenna involved in the seventh and eighth aspects, the transparent resin layer and the conductive component are the same as the transparent resin layer and the conductive component described above with respect to the laminated body and the transparent antenna involved in this embodiment. The transparent resin layer can be supported by the supporting component. In addition to the portion arranged on the conductive component, the covering component can also have a portion arranged on the transparent resin layer but not arranged on the conductive component, and can also abut against the transparent substrate and the conductive component.

[0119] In the manufacturing method of the transparent antenna involved in the above-mentioned 1st to 8th aspects, the above-mentioned steps, structures, etc. can be combined with each other for each aspect. For example, in the manufacturing method of the transparent antenna involved in the 5th aspect, the manufacturing method of the transparent antenna involved in the 4th aspect can use the above-mentioned steps, structures, etc.

[0120] The transparent antenna involved in this embodiment can be used in an image display device, a car component (windshield, rear window glass, sunroof, window, etc.), a building, etc. The image display device, car or building involved in this embodiment has the transparent antenna involved in this embodiment. The image display device can have an image display portion for displaying an image, and a frame portion (frame portion) located around the image display portion, and the transparent antenna can be arranged on the image display portion. The image display device can be used in various electronic devices such as personal computers, navigation systems (such as car navigation), mobile phones, clocks, electronic dictionaries, etc.

[0121] Figure 3 and Figure 4 It is a schematic cross-sectional view showing an example of an image display device, and shows a part of an image display portion of the image display device. Figure 3 The image display device 100 includes a transparent antenna 110 and a protective member 120 disposed on the transparent antenna 110. The transparent antenna 110 includes a transparent substrate 110a, a mesh conductive member 110b disposed on the transparent substrate 110a, and a covering member 110c disposed on the transparent substrate 110a and the conductive member 110b. Figure 4 The image display device 200 includes a transparent antenna 210 and a protective member 220 disposed on the transparent antenna 210. The transparent antenna 210 includes a transparent member 210a, a transparent substrate 210b disposed on the transparent member 210a, a mesh conductive member 210c disposed on the transparent substrate 210b, and a covering member 210d disposed on the transparent substrate 210b and the conductive member 210c. The covering members 110c and 210d cover the transparent substrates 110a and 210b and the conductive members 110b and 210c.

[0122] In the image display device 100, at least one selected from the group consisting of the transparent substrate 110a and the covering member 110c includes a cured product of the resin composition involved in the present embodiment, for example, it is formed by the cured product of the resin composition involved in the present embodiment. One of the transparent substrate 110a and the covering member 110c can be formed by a material having a total light transmittance of more than 90% per 100 μm thickness (for example, a polyolefin such as a cycloolefin polymer). In the image display device 200, at least one selected from the group consisting of the transparent substrate 210b and the covering member 210d includes a cured product of the resin composition involved in the present embodiment, for example, it is formed by the cured product of the resin composition involved in the present embodiment. One of the transparent substrate 210b and the covering member 210d can be formed by a material having a total light transmittance of more than 90% per 100 μm thickness. The conductive members 110b and 210c are formed, for example, of copper. The transparent member 210a is formed, for example, of polyolefin. The protective members 120 and 220 can be, for example, glass plates.

[0123] Example

[0124] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0125] <Preparation of resin varnish>

[0126] (Example 1)

[0127] A styrene polymer 1 (maleic anhydride-modified styrene-butadiene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Tuffprene 912, styrene content: 40% by mass) 80 parts by mass, an acrylic compound 1 (1,9-nonanediol diacrylate, manufactured by Showa Denko Materials Co., Ltd., product name: FA-129AS) 20 parts by mass, a polymerization initiator (2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, manufactured by NOF CORPORATION, product name: Perhexa 25O) 1.0 parts by mass and a solvent (toluene) 150 parts by mass were mixed while stirring to obtain a resin varnish.

[0128] (Example 2)

[0129] A resin varnish was obtained in the same manner as in Example 1 except that methacrylic compound 1 (1,9-nonanediol dimethacrylate, manufactured by SHIN-NAKAMURA CHEMICAL CO., LTD., product name: NK ESTER NOD-N) was used instead of acrylic compound 1.

[0130] (Example 3)

[0131] A resin varnish was obtained in the same manner as in Example 1 except that the methacrylic compound 2 (1,12-dodecanediol dimethacrylate, manufactured by SHIN-NAKAMURA CHEMICAL CO., LTD., product name: NK ESTER DDD) was used instead of the acrylic compound 1.

[0132] (Examples 4 to 6)

[0133] A resin varnish was obtained in the same manner as in Examples 1 to 3 except that styrene polymer 2 (styrene-butadiene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Asaflex 810, MFR (ISO 1133, 200°C, 5kgf) 5 g / 10 min, Vicat softening temperature (ISO 306, 10N, 50°C / h) 83°C) was used instead of styrene polymer 1.

[0134] (Examples 7 to 9)

[0135] A resin varnish was obtained in the same manner as in Examples 1 to 3 except that styrene polymer 3 (styrene-butadiene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Asaflex 830, MFR (ISO 1133, 200°C, 5kgf) 6 g / 10 min, Vicat softening temperature (ISO 306, 10N, 50°C / h) 72°C) was used instead of styrene polymer 1.

[0136] (Examples 10 to 12)

[0137] A resin varnish was obtained in the same manner as in Examples 1 to 3 except that styrene polymer 4 (styrene-butadiene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Asaflex 840, MFR (ISO 1133, 200°C, 5kgf) 7 g / 10 min, Vicat softening temperature (ISO 306, 10N, 50°C / h) 81°C) was used instead of styrene polymer 1.

[0138] (Example 13)

[0139] A resin varnish was obtained in the same manner as in Example 1 except that styrene polymer 5 (styrene-ethylene-butylene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Tuftec H1041, styrene content: 32 mass %) was used instead of styrene polymer 1.

[0140] (Comparative Example 1)

[0141] A resin varnish was obtained in the same manner as in Example 1 except that styrene polymer 6 (hydrogenated styrene butadiene random copolymer, manufactured by JSR Corporation, product name: DYNARON 2324P) was used instead of styrene polymer 1 and the amount of the polymerization initiator used was changed to 0.2 parts by mass.

[0142] <Evaluation of tensile elastic modulus and dielectric properties of cured products>

[0143] As a substrate film, a surface release-treated PET film (manufactured by FUJIMORI KOGYO CO., LTD., product name: HTA, thickness: 75 μm) was prepared. The above-mentioned resin varnish was applied to the release-treated surface of the PET film using a knife coater (manufactured by YASUI SEIKI CO., LTD., product name: SNC-300). Then, a resin film was formed by drying at 100° C. for 10 minutes in a dryer (manufactured by FUTABA KAGAKUIBARAKI CO., LTD., product name: MSO-80TPS). By adjusting the gap of the coater, the thickness of the dried resin film was adjusted to 100 μm. As a protective film, a surface release-treated PET film (manufactured by FUJIMORI KOGYO CO., LTD., product name: BD, thickness: 75 μm) was prepared, and then a laminated film A was obtained by attaching the release-treated surface of the protective film to the resin film.

[0144] The laminated film A was heat-treated at 120° C. for 30 minutes in a dryer (manufactured by FUTABA KAGAKU IBARAKI CO., LTD., product name: MSO-80TPS) to thermally cure the resin film, thereby obtaining an evaluation film having a base film, a cured film, and a protective film.

[0145] After cutting a laminate of 50 mm in length and 10 mm in width from the above-mentioned evaluation film, the base film and protective film of the laminate were removed to obtain a test piece. Under an environment of 25°C, the stress-strain curve of the test piece was measured using AUTOGRAPH (manufactured by Shimadzu Corporation, product name: EZ-S), and the tensile modulus was obtained from the stress-strain curve. The distance between the chucks during the measurement was set to 20 mm, and the tensile speed was set to 50 mm / min. As the tensile modulus, the value of the load between 0.5 N and 1.0 N was measured. The results are shown in Table 1.

[0146] From the above-mentioned evaluation films of Examples 1 to 12, a laminate with a length of 80 mm and a width of 80 mm was cut as a test piece, and then the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the entire test piece were measured by the separated pillar dielectric resonator method (SPDR method) at 25°C using a vector network analyzer (manufactured by Agilent Technologies Japan, Ltd., product name: E8364B) and a 10 GHz resonator (manufactured by Kanto Electronics Application and Development, Inc., product name: CP531). In addition, after making a laminate (length: 80 mm, width: 80 mm) in which only the above-mentioned substrate film and protective film were laminated, the relative dielectric constant and dielectric loss tangent of the laminate were measured by the same method. The relative dielectric constant and dielectric loss tangent of the cured film were obtained by subtracting the measurement results of the above-mentioned laminate (laminate in which only the substrate film and protective film were laminated) from the measurement results of the above-mentioned test piece. Table 1 shows the results.

[0147] <Measurement of total light transmittance>

[0148] After cutting a laminate of 30 mm in length and 30 mm in width from the above-mentioned evaluation films of Examples 1, 10 and 13, the base film and protective film of the laminate were removed to obtain a test piece. The total light transmittance (TT) of the test piece was measured using the method according to JIS K7136. Specifically, a white LED light was irradiated under an environment of 25°C, and the total light transmittance of the light transmitted through the test piece was measured. SH7000 (product name) manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd. was used as a measuring device. The total light transmittance was 91% in Example 1, 90% in Example 10, and 92% in Example 13. By the same measurement, a total light transmittance of more than 90% was also obtained in Examples other than Examples 1, 10 and 13.

[0149] <Evaluation of wrinkle appearance>

[0150] As a copper component, a laminate of copper foil A (thickness: 18 μm) and copper foil B (thickness: 2 μm) (Mitsui Mining & Smelting Co., Ltd., product name: MT-18FL) was prepared. After removing the protective film of the laminate film A, a pressurized vacuum laminator (Nikko-Materials Co., Ltd., product name: V130) was used to laminate the exposed resin film (resin film of the laminate film A) to the copper foil B of the copper component under the conditions of 0.5 MPa pressure, vacuuming for 10 seconds, and pressing for 30 seconds. After removing the substrate film (the substrate film of laminated film A), a pressurized vacuum laminator (manufactured by NIKKO-MATERIALS CO., LTD., product name: V130) was used to laminate the exposed resin film and the COP film (thickness: 100 μm) under the conditions of a pressure of 0.5 MPa, vacuuming for 10 seconds, and pressing for 30 seconds, thereby obtaining laminated film B.

[0151] The laminated film B was heat treated at 120° C. for 30 minutes in a dryer (manufactured by FUTABA KAGAKU IBARAKI CO., LTD., product name: MSO-80TPS) to thermally cure the resin film, thereby obtaining an evaluation film including a COP film, a cured film, copper foil B, and copper foil A.

[0152] A laminate of 100 mm in length and 100 mm in width was cut from the above evaluation film to obtain a test piece. Copper foil A was removed from the test piece, and the exposed copper foil B was checked for wrinkles. The case without wrinkles was evaluated as "A", and the case with wrinkles was evaluated as "B". The results are shown in Table 1.

[0153] [Table 1]

[0154]

[0155] Explanation of symbols

[0156] 10, 20, 30-laminate, 10a, 20a, 30a-base film, 10b, 20b, 30b-transparent resin layer, 10c-protective film, 20c, 30c, 30d, 110b, 210c-conductive component, 100, 200-image display device, 110, 210-transparent antenna, 110a, 210b-transparent base material, 110c, 210d-covering component, 120, 220-protective component, 210a-transparent component.

[0157] [Invention Name] Resin composition, cured product, laminate, transparent antenna and image display device [Technical field]

[0159] The present invention relates to a resin composition, a cured product, a laminate, a transparent antenna, an image display device, and the like. [Background Technology]

[0161] The antenna for receiving radio waves is provided in an image display device (for example, an image display device in various electronic devices such as a personal computer, a navigation system, a mobile phone, a clock, an electronic dictionary, etc.), a component of a car, a building, etc. For example, an image display device with a built-in antenna is sometimes used. In recent years, in order to correspond to the miniaturization, thinning, and diversification of shapes of image display devices and ensure the likelihood of design, it has been proposed to configure a transparent and low-visibility antenna (hereinafter also referred to as a "transparent antenna") on the image display portion for displaying images. Various components have been studied for components for obtaining a transparent antenna (for example, refer to the following patent document 1).

[0162] [Previous technical literature]

[0163] [Patent Document]

[0164] Patent Document 1: Japanese Patent Application Publication No. 2011-091788 [Summary of the invention]

[0166] [Technical issues to be solved by the invention]

[0167] As a component of a transparent antenna, a laminate having a cured product of a resin composition and a transparent member in contact with the cured product is sometimes used (for example, in a transparent antenna having a transparent substrate, a conductive member disposed on the transparent substrate, and a covering member disposed on the conductive member, the covering member is sometimes formed of a cured product of the resin composition). Such a cured product is required to have excellent adhesion to the transparent member.

[0168] One aspect of the present invention is to provide a resin composition that can obtain a cured product having excellent adhesion to a transparent component. Another aspect of the present invention is to provide a cured product of the resin composition. Another aspect of the present invention is to provide a laminate using the resin composition or its cured product. Another aspect of the present invention is to provide a transparent antenna using the cured product of the resin composition. Another aspect of the present invention is to provide an image display device using the transparent antenna.

[0169] [Means for solving technical problems]

[0170] The present invention is related to the following [1] to

[11] in several aspects.

[0171] [1] A resin composition comprising a styrene block copolymer, a (meth)acrylic compound and a polymerization initiator.

[0172] [2] The resin composition according to [1], wherein the styrene-based block copolymer has butadiene as a monomer unit.

[0173] [3] The resin composition according to [1] or [2], wherein the (meth)acrylic compound includes a bifunctional (meth)acrylic compound.

[0174] [4] The resin composition according to any one of [1] to [3], wherein the (meth)acrylic compound contains alkanediol di(meth)acrylate.

[0175] [5] The resin composition according to any one of [1] to [4], wherein the (meth)acrylic compound includes a compound represented by the following general formula (I).

[0176]

[0177] [In formula (I), R 1 represents a group containing 9 or less carbon atoms and 2 or more oxygen atoms, R 2a and R 2b Each independently represents a hydrogen atom or a methyl group.]

[0178] [6] The resin composition according to any one of [1] to [5], further comprising a silane compound.

[0179] [7] The resin composition according to [6], wherein the silane compound includes a silane compound having a carboxyl group.

[0180] [8] A cured product, which is a cured product of the resin composition according to any one of [1] to [7].

[0181] [9] A laminate comprising a substrate film and a transparent resin layer disposed on the substrate film, wherein the transparent resin layer comprises at least one selected from the group consisting of the resin composition according to any one of [1] to [7] and a cured product thereof.

[0182]

[10] A transparent antenna comprising a transparent substrate, a conductive component disposed on the transparent substrate, and a covering component disposed on the conductive component, wherein at least one selected from the group consisting of the transparent substrate and the covering component comprises a cured product of the resin composition described in any one of [1] to [7].

[0183]

[11] An image display device comprising the transparent antenna described in

[10] .

[0184] [Effects of the invention]

[0185] According to one aspect of the present invention, a resin composition capable of obtaining a cured product having excellent adhesion to a transparent component can be provided. According to another aspect of the present invention, a cured product of the resin composition can be provided. According to another aspect of the present invention, a laminate using the resin composition or its cured product can be provided. According to another aspect of the present invention, a transparent antenna using the cured product of the resin composition can be provided. According to another aspect of the present invention, an image display device using the transparent antenna can be provided. [Drawings]

[0187] Figure 1 It is a schematic cross-sectional view showing an example of a laminated body.

[0188] Figure 2 It is a schematic cross-sectional view showing an example of a laminated body.

[0189] Figure 3 It is a schematic cross-sectional view showing an example of an image display device.

[0190] Figure 4 It is a schematic cross-sectional view showing an example of an image display device. [Specific implementation method]

[0192] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.

[0193] In this specification, the numerical range shown by "~" indicates the range including the numerical values ​​recorded before and after "~" as the minimum and maximum values, respectively. "Above A" in the numerical range refers to A and the range exceeding A. "Below A" in the numerical range refers to A and the range less than A. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of other stages. In the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. "A or B" can include either A and B, or both. The materials exemplified in this specification are not particularly limited, and can be used alone or in combination of two or more. In this specification, with respect to the content of each component in the composition, when there are multiple substances that meet the various components in the composition, unless otherwise specified, it refers to the total amount of the multiple substances present in the composition. With respect to the term "layer", in addition to the structure of the shape formed on the entire surface when observed in a top view, it also includes the structure of the shape formed in a part. The term "process" includes independent processes, even if they cannot be clearly distinguished from other processes, as long as the intended effect of the process can be achieved. "(Meth)acryloyl" refers to at least one of acryloyl and its corresponding methacryloyl. The same applies to other similar expressions such as "(meth)acrylate". The content of (meth)acrylic compounds refers to the total amount of acrylic compounds and methacrylic compounds. Hydroxyl does not include the OH group contained in the carboxyl group.

[0194] The resin composition involved in the present embodiment contains a styrene block copolymer, a (meth) acrylic compound and a polymerization initiator. The resin composition involved in the present embodiment can be used as a resin composition for a transparent antenna. The resin composition involved in the present embodiment is a curable (photocurable, thermosetting, etc.) resin composition. The cured product involved in the present embodiment is obtained by curing the resin composition involved in the present embodiment (photocuring, thermosetting, etc.), which is a cured product (photocurable, thermosetting, etc.) of the resin composition involved in the present embodiment. The cured product involved in the present embodiment can be in a semi-cured state or a fully cured state.

[0195] According to the resin composition involved in the present embodiment, a cured product having excellent adhesion to a transparent component (e.g., a transparent substrate) can be obtained. As a constituent material of a transparent component (e.g., a transparent substrate), for example, a cycloolefin polymer (COP: Cyclo Olefin Polymer) is sometimes used, and thus, for a cured product used for a transparent antenna, it is sometimes required to have excellent adhesion to a COP component (e.g., a COP substrate). In contrast, according to one mode of the resin composition involved in the present embodiment, a cured product having excellent adhesion to a COP component (e.g., a COP substrate) can be obtained. According to one mode of the resin composition involved in the present embodiment, in a cross-cut test in the examples described later, for example, an adhesion exceeding 0 (preferably 30 or more, 50 or more, 80 or more, 90 or more, etc.) can be obtained. The resin composition involved in the present embodiment can be used for a transparent component (e.g., a transparent substrate) formed of a constituent material other than a cycloolefin polymer.

[0196] Transparent antenna can be used in the communication of the high frequency band for realizing high-speed and high-capacity communication. In the communication of high frequency band, there is a tendency that transmission loss is large. Therefore, as the constituent parts of transparent antenna, to the cured product of resin combination, it is required to have excellent dielectric properties. According to one mode of the resin combination involved in the present embodiment, it is possible to obtain a cured product with excellent relative dielectric constant (low relative dielectric constant). And, according to one mode of the resin combination involved in the present embodiment, it is possible to obtain a cured product with excellent dielectric loss tangent (low dielectric loss tangent).

[0197] According to one aspect of the resin composition of the present embodiment, a cured product having excellent moisture and heat resistance can be obtained. For example, according to one aspect of the resin composition of the present embodiment, a cured product having excellent transmittance can be obtained even when exposed to high temperature and high humidity.

[0198] The resin composition involved in the present embodiment contains a styrene block copolymer.Styrene block copolymers are block copolymers having styrene compounds and compounds different from styrene compounds as monomer units (block copolymers having monomer units derived from styrene compounds and monomer units derived from compounds different from styrene compounds), and are block copolymers having a polymer chain (segment) containing styrene compounds as monomer units and a polymer chain (segment) containing compounds different from styrene compounds as monomer units. It is inferred that the monomer unit of styrene compounds contributes to the improvement of adhesion, and the monomer units (forming polymer chains) are concentrated in styrene block copolymers, thus easily obtaining excellent adhesion. However, the main reason for obtaining excellent adhesion is not limited to the content. In the case where a styrene block copolymer has a plurality of polymer chains containing styrene compounds as monomer units, these polymer chains can contain the same styrene compounds as monomer units, or can contain different styrene compounds as monomer units. It is also the same for polymer chains containing compounds different from styrene compounds as monomer units.Styrene block copolymers can be elastomers.

[0199] Examples of the styrene compound include styrene; alkyl styrenes such as methyl styrene, dimethyl styrene, trimethyl styrene, ethyl styrene, diethyl styrene, triethyl styrene, propyl styrene, butyl styrene, hexyl styrene, heptyl styrene, and octyl styrene; halogenated styrenes such as fluorostyrene, chlorostyrene, bromostyrene, dibromostyrene, and iodostyrene; nitrostyrene; acetylstyrene; methoxystyrene, etc. From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance (total light transmittance, etc.; the same below) and dielectric properties (relative dielectric constant, dielectric loss tangent, etc.; the same below) in the cured product, the styrene block copolymer may have styrene as a monomer unit.

[0200] As compounds different from styrene compounds, there can be mentioned conjugated dienes such as butadiene and isoprene; olefins such as ethylene and propylene; maleic anhydride, etc. From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance, and dielectric properties in the cured product, the styrene block copolymer may have a conjugated diene as a monomer unit, or may have butadiene as a monomer unit.

[0201] Examples of styrene block copolymers include styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-ethylene-butylene-styrene block copolymers, styrene-ethylene-propylene-styrene block copolymers, and hydrogenated copolymers thereof. Styrene block copolymers may be modified with an acid anhydride (maleic anhydride, etc.).

[0202] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the content of the monomer unit of the styrene compound in the styrene block copolymer can be within the following range based on the total mass of the monomer units constituting the styrene block copolymer. The content of the monomer unit of the styrene compound can be more than 0 mass%, more than 1 mass%, more than 5 mass%, more than 10 mass%, more than 15 mass%, more than 20 mass%, more than 25 mass%, more than 30 mass%, more than 35 mass% or more than 40 mass%. The content of the monomer unit of the styrene compound can be less than 100 mass%, less than 90 mass%, less than 80 mass%, less than 70 mass%, less than 65 mass%, less than 60 mass%, less than 55 mass%, less than 50 mass%, less than 45 mass% or less than 40 mass%. From these viewpoints, the content of the monomer unit of the styrene compound can be more than 0 mass% and less than 100 mass%, 10 to 80 mass%, 20 to 60 mass% or 30 to 50 mass%.

[0203] In the case where the styrene block copolymer has butadiene as a monomer unit, from the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the content of the monomer unit of butadiene in the styrene block copolymer can be within the following range based on the total mass of the monomer units constituting the styrene block copolymer. The content of the monomer unit of butadiene can be more than 0% by mass, 10% by mass or more, 20% by mass or more, 30% by mass or more, 35% by mass or more, 40% by mass or more, 45% by mass or more, 50% by mass or more, 55% by mass or more or 60% by mass or more. The content of the monomer unit of butadiene can be less than 100% by mass, 99% by mass or less, 95% by mass or less, 90% by mass or less, 85% by mass or less, 80% by mass or less, 75% by mass or less, 70% by mass or less, 65% by mass or less or 60% by mass or less. From these viewpoints, the content of the butadiene monomer unit may be more than 0 mass % and less than 100 mass %, 20 to 90 mass %, 40 to 80 mass %, or 50 to 70 mass %.

[0204] Based on the total mass of the resin composition (excluding the mass of the organic solvent) or the total amount of the styrene block copolymer, the (meth) acrylic compound and the polymerization initiator, the content of the styrene block copolymer can be within the following range. From the viewpoint of easily obtaining excellent moisture and heat resistance and dielectric properties in the cured product, the content of the styrene block copolymer can be 30% by mass or more, 40% by mass or more, 50% by mass or more, more than 50% by mass, 60% by mass or more, 65% by mass or more, 70% by mass or more, 75% by mass or more, 76% by mass or more, 78% by mass or more or 80% by mass or more. The content of the styrene block copolymer can be 95% by mass or less, 90% by mass or less, 85% by mass or less, 80% by mass or less, 78% by mass or less or 76% by mass or less. From these viewpoints, the content of the styrene block copolymer can be 30 to 95% by mass, 40 to 90% by mass or 50 to 85% by mass.

[0205] Based on the total amount of the styrene block copolymer and the (meth) acrylic compound, the content of the styrene block copolymer may be within the following range. From the viewpoint of easily obtaining excellent moisture and heat resistance and dielectric properties in the cured product, the content of the styrene block copolymer may be 30% by mass or more, 40% by mass or more, 50% by mass or more, more than 50% by mass, 60% by mass or more, 65% by mass or more, 70% by mass or more, 75% by mass or more, 80% by mass or more, 82% by mass or more, or 85% by mass or more. The content of the styrene block copolymer may be 99% by mass or less, 95% by mass or less, 90% by mass or less, 85% by mass or less, 82% by mass or less, or 80% by mass or less. From these viewpoints, the content of the styrene block copolymer may be 30 to 99% by mass, 50 to 95% by mass, or 70 to 90% by mass.

[0206] The resin composition according to the present embodiment may contain a (meth)acrylic compound. The (meth)acrylic compound is a compound having a (meth)acryloyl group. The (meth)acrylic compound may or may not have an epoxy group.

[0207] The (meth)acrylic compound may include at least one selected from the group consisting of a monofunctional (meth)acrylic compound and a polyfunctional (meth)acrylic compound (a bifunctional (meth)acrylic compound or a trifunctional or higher (meth)acrylic compound). For example, a "bifunctional (meth)acrylic compound" refers to a compound having a total of two acryloyl groups and two methacryloyl groups in one molecule. From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance, and dielectric properties in a cured product, the (meth)acrylic compound may include a bifunctional (meth)acrylic compound.

[0208] Examples of the monofunctional (meth)acrylic acid compound include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, butoxyethyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octylheptyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, and (meth)acrylate. aliphatic (meth)acrylates such as stearyl (meth)acrylate, behenyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, and mono(2-(meth)acryloyloxyethyl)succinate; cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and (meth)acrylate. alicyclic (meth)acrylates such as isobornyl (meth)acrylate, mono(2-(meth)acryloyloxyethyl)tetrahydrophthalic acid, mono(2-(meth)acryloyloxyethyl)hexahydrophthalic acid; benzyl (meth)acrylate, phenyl (meth)acrylate, o-biphenyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, p-isopropylphenylphenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, 1-naphthyloxyethyl (meth)acrylate, 2-naphthyloxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate Aromatic (meth)acrylates such as esters, (meth)acrylate phenoxypolypropylene glycol ester, (meth)acrylate 2-hydroxy-3-phenoxypropyl ester, (meth)acrylate 2-hydroxy-3-(o-phenylphenoxy)propyl ester, (meth)acrylate 2-hydroxy-3-(1-naphthyloxy)propyl ester, (meth)acrylate 2-hydroxy-3-(2-naphthyloxy)propyl ester; heterocyclic (meth)acrylates such as (meth)acrylate 2-tetrahydrofurfuryl ester, N-(meth)acryloyloxyethyl hexahydrophthalimide, 2-(meth)acryloyloxyethyl-N-carbazole; (meth)acryloyl group-containing phosphates (e.g., (meth)acryloyloxyethyl acid phosphate); these caprolactone modified products, etc.

[0209] Examples of the bifunctional (meth)acrylic compound include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1 aliphatic (meth)acrylates (e.g., alkanediol di(meth)acrylates) such as 6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, nonanediol di(meth)acrylate (e.g., 1,9-nonanediol di(meth)acrylate), decanediol di(meth)acrylate (e.g., 1,10-decanediol di(meth)acrylate), dodecanediol di(meth)acrylate (e.g., 1,12-dodecanediol di(meth)acrylate), glycerol di(meth)acrylate, ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate, and the like; cyclohexanedimethanol di(meth)acrylate, ethoxylated cyclohexanedimethanol di(meth)acrylate, and the like; acrylate, propoxylated cyclohexanedimethanol di(meth)acrylate, ethoxylated propoxylated cyclohexanedimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethoxylated tricyclodecane dimethanol di(meth)acrylate, propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated hydrogenated bisphenol A di(meth)acrylate, propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated hydrogenated bisphenol F di(meth)acrylate, propoxylated hydrogenated bisphenol F di(meth)acrylate, ethoxylated propoxylated hydrogenated bisphenol F di(meth)acrylate Alicyclic (meth)acrylates such as acrylates; aromatic (meth)acrylates such as ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated bisphenol AF di(meth)acrylate, propoxylated bisphenol AF di(meth)acrylate, ethoxylated propoxylated bisphenol AF di(meth)acrylate, ethoxylated fluorene di(meth)acrylate, propoxylated fluorene di(meth)acrylate, and ethoxylated propoxylated fluorene di(meth)acrylate;Heterocyclic (meth)acrylates such as dioxypropylene glycol di(meth)acrylate, ethoxylated isocyanuric acid di(meth)acrylate, propoxylated isocyanuric acid di(meth)acrylate, and ethoxylated propoxylated isocyanuric acid di(meth)acrylate; these caprolactone modified products; aliphatic epoxy (meth)acrylates such as neopentyl glycol epoxy (meth)acrylate; alicyclic epoxy (meth)acrylates such as cyclohexanedimethanol epoxy (meth)acrylate, hydrogenated bisphenol A epoxy (meth)acrylate, and hydrogenated bisphenol F epoxy (meth)acrylate; aromatic epoxy (meth)acrylates such as resorcinol epoxy (meth)acrylate, bisphenol A epoxy (meth)acrylate, bisphenol F epoxy (meth)acrylate, bisphenol AF epoxy (meth)acrylate, and fluorene epoxy (meth)acrylate, etc.;

[0210] Examples of the trifunctional or higher-functional (meth)acrylic compound include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and ethoxylated propoxylated pentaerythritol tri(meth)acrylate. Aliphatic (meth)acrylates such as oxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, and propoxylated dipentaerythritol hexa(meth)acrylate; heterocyclic (meth)acrylates such as ethoxylated isocyanurate tri(meth)acrylate, propoxylated isocyanurate tri(meth)acrylate, and ethoxylated propoxylated isocyanurate tri(meth)acrylate; these caprolactone modified products; aromatic epoxy (meth)acrylates such as phenol novolac type epoxy (meth)acrylate and cresol novolac type epoxy (meth)acrylate, etc.

[0211] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the (meth) acrylic compound may include a monofunctional or polyfunctional (e.g., bifunctional) aliphatic (meth) acrylic compound (aliphatic (meth) acrylate). From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the (meth) acrylic compound may include an alkanediol di(meth) acrylate. From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the (meth) acrylic compound may include at least one selected from the group consisting of nonanediol di(meth) acrylate, decanediol di(meth) acrylate, dodecanediol di(meth) acrylate and tricyclodecane dimethanol di(meth) acrylate, and may also include nonanediol di(meth) acrylate. From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the (meth) acrylic compound may include an acrylic compound.

[0212] The (meth)acrylic compound may contain a compound represented by the following general formula (I) from the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance, and dielectric properties in the cured product.

[0213]

[0214] [In formula (I), R 1 represents a group containing 9 or less carbon atoms and 2 or more oxygen atoms, R 2a and R 2b Each independently represents a hydrogen atom or a methyl group.]

[0215] R 1 The carbon atoms of R are 1 to 9. From the viewpoint of obtaining excellent adhesion, moisture and heat resistance, and dielectric properties in the cured product, R 1 The carbon atoms of R may be 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, or 8 or more. From the viewpoint of obtaining excellent adhesion, moisture and heat resistance, and dielectric properties in the cured product, R 1 The oxygen atoms may be 6 or less, 5 or less, 4 or less, 3 or less, or 2 or less. 1 It can be a hydrocarbon group with oxygen atoms bonded at both ends, or it can be a "-OC n H 2n -O-" group (n=1 to 9).

[0216] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the content of the compound represented by the general formula (I) can be 50% by mass or more, 70% by mass or more, 90% by mass or more, 95% by mass or more or 99% by mass or more, based on the total mass of the (meth)acrylic compounds (the total amount of the (meth)acrylic compounds contained in the resin composition). The (meth)acrylic compounds contained in the resin composition are substantially composed of compounds represented by the general formula (I) (based on the total mass of the (meth)acrylic compounds contained in the resin composition, the content of the compound represented by the general formula (I) is substantially 100% by mass).

[0217] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the (meth)acrylic compound may contain a (meth)acrylic compound having a molecular weight within the following range. The molecular weight of the (meth)acrylic compound may be 80 or more, 100 or more, 120 or more, 150 or more, 180 or more, 200 or more, 220 or more, 250 or more or 260 or more. The molecular weight of the (meth)acrylic compound may be 1000 or less, 800 or less, 600 or less, 550 or less, 500 or less, 450 or less, 400 or less, 350 or less, 320 or less, 300 or less, 280 or less or 270 or less. From these viewpoints, the molecular weight of the (meth)acrylic compound may be 80 to 1000, 100 to 600, 100 to 500, 250 to 600 or 200 to 400.

[0218] Based on the total mass of the resin composition (excluding the mass of the organic solvent) or the total amount of the styrene block copolymer, the (meth) acrylic acid compound and the polymerization initiator, the content of the (meth) acrylic acid compound can be within the following range. From the viewpoint of easily obtaining excellent moisture-heat resistance and dielectric properties in the cured product, the content of the (meth) acrylic acid compound can be 50% by mass or less, less than 50% by mass, 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, 19% by mass or less, 18% by mass or less or 15% by mass or less. The content of the (meth) acrylic acid compound can be 1% by mass or more, 5% by mass or more, 10% by mass or more, 15% by mass or more, 18% by mass or more or 19% by mass or more. From these viewpoints, the content of the (meth) acrylic acid compound can be 1 to 50% by mass, 5 to 40% by mass or 10 to 30% by mass.

[0219] Based on the total amount of the styrene block copolymer and the (meth) acrylic acid compound, the content of the (meth) acrylic acid compound can be within the following range. From the viewpoint of easily obtaining excellent moisture and heat resistance and dielectric properties in the cured product, the content of the (meth) acrylic acid compound can be 70% by mass or less, 60% by mass or less, 50% by mass or less, less than 50% by mass, 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, 18% by mass or less or 15% by mass or less. The content of the (meth) acrylic acid compound can be 1% by mass or more, 5% by mass or more, 10% by mass or more, 15% by mass or more, 18% by mass or more or 20% by mass or more. From these viewpoints, the content of the (meth) acrylic acid compound can be 1 to 70% by mass, 5 to 50% by mass or 10 to 30% by mass.

[0220] The resin composition involved in the present embodiment contains a polymerization initiator. As a polymerization initiator, as long as it is a compound that initiates polymerization by irradiation of active light (ultraviolet rays, etc.), heating, etc., it is not particularly limited, but for example, photopolymerization initiators and thermal polymerization initiators can be cited. One of the photopolymerization initiator and the thermal polymerization initiator can be used, and the photopolymerization initiator and the thermal polymerization initiator can also be used together. From the viewpoint of being able to perform room temperature curing, the polymerization initiator can be a photopolymerization initiator.

[0221] Examples of the photopolymerization initiator include photoradical generators, photobase generators, photoacid generators, etc. The photopolymerization initiator may contain a photoradical initiator from the viewpoint of easily obtaining excellent adhesion, moisture-heat resistance, and dielectric properties in a cured product.

[0222] Examples of the photopolymerization initiator include acylphosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; benzoin compounds such as benzoin, benzoin methyl ether, and benzoin isopropyl ether; acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexylphenyl ketone, 2-benzyl-2-dimethylamino-1 -(4-morpholinophenyl)-butanone-1, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propane, N,N-dimethylaminoacetophenone and other acetophenone compounds; 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-amylanthraquinone, 2-aminoanthraquinone and other anthraquinone compounds; acetophenone dimethyl ketal, benzyl dimethyl ketal and other ketal compounds; benzophenone, methyl benzophenone, 4,4'-dichlorobenzophenone, 4,4'-bis(diethylamino)benzophenone, Michler's ketone, 4-benzoyl-4'-methyldiphenyl Benzophenone compounds such as thioethers; imidazole compounds such as 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer, 2,4-di(p-methoxyphenyl)-5-phenylimidazole dimer, 2-(2,4-dimethoxyphenyl)-4,5-diphenylimidazole dimer; 9-phenylacrylamide acridinium compounds such as 1,7-bis(9,9'-acridinyl)heptane; oxime ester compounds such as 1,2-octanedione-1-[4-(phenylthio)phenyl]-2-(o-benzoyl oxime), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone-1-(o-acetyl oxime), 1-phenyl-1,2-propanedione-2-[o-(ethoxycarbonyl)oxime]; and tertiary amine compounds such as ethyl N,N-dimethylaminobenzoate, isopentyl N,N-dimethylaminobenzoate, amyl-4-dimethylaminobenzoate, triethylamine, and triethanolamine.

[0223] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance, and dielectric properties in the cured product, the photopolymerization initiator may contain an acylphosphine oxide, may contain a bisacylphosphine oxide, may contain at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and may contain bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0224] Examples of the thermal polymerization initiator include thermal radical polymerization initiators, thermal cationic polymerization initiators, etc. Examples of the thermal polymerization initiator include ketone peroxides, peroxyketals, hydroperoxide, dialkyl peroxides, diacyl peroxides, peroxycarbonates, peroxyesters, acid anhydrides, and azo compounds.

[0225] The content of the polymerization initiator (the total amount of polymerization initiators such as photopolymerization initiators and thermal polymerization initiators; the same below) or the content of the photopolymerization initiator may be within the following ranges based on the total mass of the resin composition (excluding the mass of the organic solvent), the total amount of the styrene block copolymer, the (meth) acrylic compound and the polymerization initiator, or the total amount of the styrene block copolymer, the (meth) acrylic compound and the photopolymerization initiator. From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product and the viewpoint of easily obtaining excellent curing properties, the content of the polymerization initiator or the content of the photopolymerization initiator may be 0.1% by mass or more, 0.3% by mass or more, 0.5% by mass or more, 0.8% by mass or more, 1% by mass or more, 1.2% by mass or more, or 1.4% by mass or more. From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the content of the polymerization initiator or the content of the photopolymerization initiator can be 10% by mass or less, 8% by mass or less, 5% by mass or less, 4% by mass or less, 3% by mass or less, 2% by mass or less or 1.5% by mass or less. From these viewpoints, the content of the polymerization initiator or the content of the photopolymerization initiator can be 0.1 to 10% by mass, 0.3 to 5% by mass or 0.5 to 3% by mass.

[0226] Based on the total amount of the styrene block copolymer and the (meth) acrylic acid compound, the content of the polymerization initiator or the content of the photopolymerization initiator can be within the following range. From the perspective of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product and the perspective of easily obtaining excellent curing properties, the content of the polymerization initiator or the content of the photopolymerization initiator can be 0.1% by mass or more, 0.3% by mass or more, 0.5% by mass or more, 0.8% by mass or more, 1% by mass or more, 1.2% by mass or more or 1.5% by mass or more. From the perspective of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the content of the polymerization initiator or the content of the photopolymerization initiator can be 10% by mass or less, 8% by mass or less, 5% by mass or less, 4% by mass or less, 3% by mass or less, 2% by mass or less or 1.5% by mass or less. From these viewpoints, the content of the polymerization initiator or the content of the photopolymerization initiator can be 0.1 to 10% by mass, 0.3 to 5% by mass or 0.5 to 3% by mass.

[0227] The resin composition involved in this embodiment may contain a silane compound (except for compounds corresponding to the styrene block copolymer or the (meth) acrylic acid compound). By using the silane compound, it is easy to obtain excellent adhesion, moisture and heat resistance and dielectric properties in the cured product. The silane compound can be a silane coupling agent.

[0228] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the silane compound may include a siloxane compound (a compound having a siloxane bond). From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the number of siloxane bonds in the siloxane compound may be 1 to 4, 1 to 3 or 1 to 2. From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the number of silicon atoms in the silane compound may be 1 to 4, 1 to 3 or 1 to 2.

[0229] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the silane compound may contain a hydroxyl silane compound (a silane compound having a hydroxyl group bonded to a silicon atom). From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the number of hydroxyl groups in the silane compound may be within the following range. The number of hydroxyl groups may be 1 or more, 2 or more, 3 or more or 4 or more. The number of hydroxyl groups may be 8 or less, 6 or less, 5 or less or 4 or less. From these viewpoints, the number of hydroxyl groups may be 1 to 8, 2 to 6, 3 to 5, 1 to 4 or 4 to 8.

[0230] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the silane compound may include a silane compound having a carboxyl group (e.g., a siloxane compound), or may include a silane compound having an organic group containing a carboxyl group while being bonded to a silicon atom (e.g., a siloxane compound). The silane compound may be a silane compound having a carboxyl group bonded to a silicon atom (e.g., a siloxane compound). From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the number of carboxyl groups in the silane compound may be 1 to 4, 1 to 3 or 1 to 2.

[0231] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the content of the silane compound can be within the following range based on the total mass of the resin composition (excluding the mass of the organic solvent) or the total amount of the styrene block copolymer, the (meth) acrylic compound and the polymerization initiator. The content of the silane compound can be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 1.5% by mass or more, 2% by mass or more, 2.5% by mass or more or 2.8% by mass or more. The content of the silane compound can be 10% by mass or less, 8% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, 3.5% by mass or less or 3% by mass or less. From these viewpoints, the content of the silane compound can be 0.1 to 10% by mass, 0.5 to 8% by mass or 1 to 5% by mass.

[0232] From the viewpoint of easily obtaining excellent adhesion, moisture and heat resistance and dielectric properties in the cured product, the content of the silane compound can be within the following range based on the total amount of the styrene block copolymer and the (meth) acrylic compound. The content of the silane compound can be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 1.5% by mass or more, 2% by mass or more, 2.5% by mass or more or 3% by mass or more. The content of the silane compound can be 10% by mass or less, 8% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, 3.5% by mass or less or 3% by mass or less. From these viewpoints, the content of the silane compound can be 0.1 to 10% by mass, 0.5 to 8% by mass or 1 to 5% by mass.

[0233] The resin composition involved in this embodiment may contain a tetrazole compound (except a compound having a tetrazole ring; a compound corresponding to a styrene block copolymer, a (meth) acrylic compound or a silane compound), or may not contain a tetrazole compound. By using a tetrazole compound, excellent adhesion is easily obtained in the cured product.

[0234] Examples of the tetrazole compound include 1H-tetrazole, 5-amino-1H-tetrazole, 5-methyl-1H-tetrazole, 5-(2-aminophenyl)-1H-tetrazole, 5-phenyl-1H-tetrazole, 5-mercapto-1H-tetrazole, 1-methyl-5-mercapto-1H-tetrazole, 1-methyl-5-methyltetrazole, 1-methyl-5-aminotetrazole, 1-methyl-5-mercaptotetrazole, 1-methyl-5-benzoyl-1H-tetrazole, 1-carboxymethyl-5-amino-tetrazole, 1-cyclohexyl-5-mercaptotetrazole, 1-phenyltetrazole, 1-phenyl-5-mercaptotetrazole, 1-carboxymethyl-5-mercaptotetrazole, 1,5-pentamethylenetetrazole, 1-(2-dimethylaminoethyl)-5-mercaptotetrazole, and 2-methoxy-5-(5-trifluoromethyl-1H-tetrazol-1-yl)-benzaldehyde. From the viewpoint of easily obtaining excellent adhesion in the cured product, the tetrazole compound may include a tetrazole compound having at least one selected from the group consisting of an amino group and a mercapto group, may include at least one selected from the group consisting of 5-amino-1H-tetrazole, 5-mercapto-1H-tetrazole and 1-methyl-5-mercapto-1H-tetrazole, or may include at least one selected from the group consisting of 5-amino-1H-tetrazole and 1-methyl-5-mercapto-1H-tetrazole. From the viewpoint of easily obtaining excellent transmittance in the cured product, the tetrazole compound may include a tetrazole compound having an amino group, or may include 5-amino-1H-tetrazole.

[0235] From the viewpoint of easily obtaining excellent adhesion in the cured product, based on the total mass of the resin composition (excluding the mass of the organic solvent) or the total amount of the styrene block copolymer, the (meth) acrylic acid compound and the polymerization initiator, the content of the tetrazole compound can be within the following range. The content of the tetrazole compound can be 0.01% by mass or more, 0.05% by mass or more, 0.1% by mass or more, 0.2% by mass or more, 0.3% by mass or more, 0.4% by mass or more, 0.5% by mass or more, 0.6% by mass or more, 0.7% by mass or more, 0.8% by mass or more or 0.9% by mass or more. The content of the tetrazole compound can be 10% by mass or less, 8% by mass or less, 5% by mass or less, 4% by mass or less, 3% by mass or less, 2.5% by mass or less, 2% by mass or less, 1.5% by mass or less or 1% by mass or less. From these viewpoints, the content of the tetrazole compound can be 0.01 to 10% by mass, 0.1 to 5% by mass or 0.5 to 3% by mass.

[0236] From the viewpoint of easily obtaining excellent adhesion in the cured product, the content of the tetrazole compound can be within the following range based on the total amount of the styrene block copolymer and the (meth) acrylic acid compound. The content of the tetrazole compound can be 0.01% by mass or more, 0.05% by mass or more, 0.1% by mass or more, 0.2% by mass or more, 0.3% by mass or more, 0.4% by mass or more, 0.5% by mass or more, 0.6% by mass or more, 0.7% by mass or more, 0.8% by mass or more or 0.9% by mass or more. The content of the tetrazole compound can be 10% by mass or less, 8% by mass or less, 5% by mass or less, 4% by mass or less, 3% by mass or less, 2.5% by mass or less, 2% by mass or less, 1.5% by mass or less or 1% by mass or less. From these viewpoints, the content of the tetrazole compound can be 0.01 to 10% by mass, 0.1 to 5% by mass or 0.5 to 3% by mass.

[0237] The resin composition involved in the present embodiment can contain additives other than styrene block copolymers, (methyl) acrylic compounds, polymerization initiators, silane compounds and tetrazole compounds. As such additives, polymerizable compounds, curing accelerators, antioxidants, ultraviolet absorbers, visible light absorbers, colorants, plasticizers, stabilizers, fillers (fillers), reducing agents, bicarbonates, etc. can be cited. As polymerizable compounds, halogenated vinylene, vinyl ether, vinyl ester, vinyl pyridine, vinyl amide and aryl vinyl can be cited. As reducing agents, vanadium acetylacetonate, vanadium acetylacetonate, cobalt acetylacetonate, copper acetylacetonate, vanadium cyclohexaneate, vanadium stearate, copper cyclohexaneate, cupric acetate, cobalt octoate, etc. can be cited.

[0238] Based on the total amount of the styrene block copolymer and the (meth) acrylic acid compound, the content of the filler may be 100% by mass or less, less than 100% by mass, 50% by mass or less, 20% by mass or less, less than 20% by mass, 10% by mass or less, 1% by mass or less, 0.1% by mass or less, or substantially 0% by mass. The content of the reducing agent may be 0.01% by mass or less, less than 0.01% by mass, 0.001% by mass or less, or substantially 0% by mass, relative to 100 parts by mass of the (meth) acrylic acid compound. The content of the bicarbonate may be 0.1% by mass or less, less than 0.1% by mass, 0.01% by mass or less, 0.001% by mass or substantially 0% by mass, relative to 100 parts by mass of the (meth) acrylic acid compound.

[0239] The resin composition involved in this embodiment may contain an organic solvent. The resin composition involved in this embodiment can be used as a resin varnish by diluting with an organic solvent. As an organic solvent, aromatic hydrocarbons such as toluene, xylene, mesitylene, isopropylbenzene, and p-isopropylbenzene can be cited; cyclic ethers such as tetrahydrofuran and 1,4-dioxane; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and 4-hydroxy-4-methyl-2-pentanone; esters such as methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, and γ-butyrolactone; carbonates such as ethylene carbonate and propylene carbonate; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0240] The total light transmittance per 8 μm thickness of the layer containing the resin composition involved in the present embodiment or the cured product involved in the present embodiment can be 90% or more or 91% or more. The total light transmittance can be measured according to the method specified in JIS K7136, for example, using NDH-5000 (product name) manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd. The total light transmittance described below can also be measured using the same method.

[0241] The laminated body according to the present embodiment includes a base film (support film) and a transparent resin layer disposed on the base film, and the transparent resin layer includes at least one selected from the group consisting of the resin composition according to the present embodiment and a cured product thereof.

[0242] As the constituent material of the substrate film, polyester (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, etc.), polyolefin (polyethylene, polypropylene, cycloolefin polymer, etc.), polycarbonate, polyamide, polyimide, polyamideimide, polyetherimide, polyether sulfide, polyether sulfone, polyether ketone, polyphenylene ether, polyphenylene sulfide, etc. can be mentioned. The thickness of the substrate film can be 1 to 200 μm, 10 to 100 μm, 20 to 80 μm or 20 to 50 μm.

[0243] From the viewpoint of easily obtaining excellent transmittance and easily thinning the transparent antenna, the thickness of the transparent resin layer can be 1000 μm or less, 800 μm or less, 500 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 80 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 15 μm or less, 12 μm or less, 10 μm or less, 9 μm or less or 8 μm or less. From the perspective of reducing transmission loss and facilitating improving antenna characteristics, the thickness of the transparent resin layer can be greater than 0.1 μm, greater than 0.5 μm, greater than 0.75 μm, greater than 1 μm, greater than 2 μm, greater than 3 μm, greater than 5 μm, greater than 6 μm, greater than 7 μm, greater than 8 μm, greater than 10 μm, greater than 20 μm, greater than 30 μm, greater than 40 μm, greater than 50 μm, greater than 80 μm or greater than 100 μm. From these viewpoints, the thickness of the transparent resin layer can be 0.1 to 1000 μm, 1 to 1000 μm, 10 to 500 μm, 20 to 200 μm, 50 to 200 μm, 0.1 to 500 μm, 0.1 to 100 μm, 0.5 to 250 μm, 0.5 to 150 μm, 0.75 to 100 μm, 1 to 50 μm, 2 to 30 μm, 3 to 20 μm or 5 to 20 μm.

[0244] A first aspect of the laminated body according to the present embodiment may include a protective film disposed on the transparent resin layer. A second aspect of the laminated body according to the present embodiment may include a conductive member disposed on the transparent resin layer.

[0245] As the constituent material of the protective film, the constituent materials mentioned above as the constituent material of the base film can be used. The protective film can be the same film as the base film or a film different from the base film. The thickness of the protective film can be 1 to 200 μm, 10 to 100 μm, 20 to 80 μm or 20 to 50 μm.

[0246] The conductive component may be solid or may have a patterned portion (may be patterned). In a conductive component having a patterned portion (hereinafter referred to as a "patterned conductive component"), a portion or all of the conductive component may be patterned (the same also applies to the following description related to the case where the conductive component has a patterned portion). Examples of the shape of the patterned portion include a mesh shape, a spiral shape, and the like. In the case of using a transparent antenna having a solid conductive component, the conductive component may be patterned (e.g., mesh processing). The patterned (e.g., mesh) conductive component may be composed of wires (e.g., metal wires). Examples of the constituent materials of the conductive component include metal materials, carbon materials (e.g., graphene), conductive polymers, and the like. Examples of metal materials include copper, silver, gold, and the like. From the viewpoint of easily obtaining excellent conductivity and easily reducing manufacturing costs, the conductive component may contain copper.

[0247] The conductive component can be a single layer or a multilayer. The multilayer conductive component can, for example, have a first conductive component (e.g., a metal component) disposed on a transparent resin layer, and a second conductive component (e.g., a metal component) disposed on the first conductive component. At least one selected from the group consisting of the first conductive component and the second conductive component can be solid, or it can have a patterned (e.g., mesh) portion. The second conductive component can be used as a protective layer to suppress contamination, damage, etc. of the first conductive component, thereby also being able to improve the operability of the laminate. At least one selected from the group consisting of the first conductive component and the second conductive component can contain copper.

[0248] The thickness of the conductive component (the total thickness in the case where the conductive component is multi-layered), the thickness of the first conductive component or the thickness of the second conductive component can be within the following range. From the perspective that the conductive component is not easily damaged and that a solid conductive component is easily patterned (e.g., mesh processing), the thickness can be 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 18 μm or less, 15 μm or less, 10 μm or less, 8 μm or less, 5 μm or less, 3 μm or less or 2 μm or less. From the perspective of easily obtaining excellent elongation, the thickness can be 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, 0.8 μm or more, 1 μm or more, 1.2 μm or more, 1.5 μm or more or 2 μm or more. From these viewpoints, the thickness may be 0.1 to 50 μm, 0.1 to 30 μm, 0.1 to 20 μm, 0.1 to 10 μm, 0.5 to 5 μm or 1 to 3 μm.

[0249] The thickness of the first conductive component may be smaller than the thickness of the second conductive component. In the case where the conductive component is multi-layered, the thickness (total thickness) of the conductive component or the thickness of the second conductive component may be greater than 3 μm, greater than 5 μm, greater than 8 μm, greater than 10 μm, greater than 15 μm, greater than 18 μm or greater than 20 μm.

[0250] The laminated body involved in the second embodiment may include a protective film disposed on the conductive component. As the protective film, the protective film described above can be used as the protective film in the laminated body involved in the first embodiment. A demoulding treatment may be applied to at least a portion of one side of the conductive component side in the protective film, or a peeling layer may be configured on at least a portion of one side of the conductive component side in the protective film. For example, the laminated body involved in the second embodiment may include a substrate film, a transparent resin layer, a conductive component and a protective film, the conductive component is a single layer, and a demoulding treatment is applied to at least a portion of one side of the conductive component side in the protective film.

[0251] In the laminated body involved in the second embodiment, as a layer comprising at least one selected from the group consisting of a photosensitive composition and a cured product thereof, a layer L disposed on a conductive component may be provided. The photosensitive composition has photosensitivity to active light (ultraviolet rays, etc.), and may have positive photosensitivity or negative photosensitivity. The photosensitive composition may have photocurability that is cured by light irradiation. Layer L may be either before or after light irradiation, or may have at least one selected from the group consisting of an uncured portion and a cured portion. Layer L may be either before or after light irradiation, or may have at least one selected from the group consisting of an unexposed portion and an exposed portion. The constituent material of the photosensitive composition is not particularly limited.

[0252] Figure 1 and Figure 2 It is a schematic cross-sectional view showing an example of a laminated body. Figure 1 The laminate 10 of (a) includes a base film 10a, a transparent resin layer 10b disposed on the base film 10a, and a protective film 10c disposed on the transparent resin layer 10b. The transparent resin layer 10b is formed of the resin composition according to the present embodiment or the cured product according to the present embodiment. Figure 1 The laminate 20 of (b) includes a base film 20a, a transparent resin layer 20b disposed on the base film 20a, and a conductive member 20c disposed on the transparent resin layer 20b. The transparent resin layer 20b is formed of the resin composition according to the present embodiment or the cured product according to the present embodiment. Figure 2The laminate 30 includes a substrate film 30a, a transparent resin layer 30b disposed on the substrate film 30a, a conductive member 30c disposed on the transparent resin layer 30b, and a conductive member 30d disposed on the conductive member 30c. The transparent resin layer 30b is formed of the resin composition involved in this embodiment or the cured product involved in this embodiment.

[0253] The resin composition and cured product thereof according to the present embodiment can be used in a transparent antenna and a method for manufacturing the same. In a transparent antenna, the applicable part of the resin composition and cured product thereof according to the present embodiment is not particularly limited. Regarding the case of using the resin composition according to the present embodiment, hereinafter, the substrate obtained by curing the resin composition of the transparent resin layer in the curing process is referred to as a "transparent substrate", and the layer that can contain the state before curing the resin composition of the transparent resin layer in the curing process is referred to as a "transparent resin layer".

[0254] The first mode of the transparent antenna involved in the present embodiment comprises a transparent substrate, a conductive component arranged on the transparent substrate, and a covering component (transparent component) arranged on the conductive component, and the transparent substrate comprises a cured product of the resin composition involved in the present embodiment. In the transparent antenna involved in the first mode, the covering component (transparent component) may include a cured product of the resin composition involved in the present embodiment, or may not include a cured product of the resin composition involved in the present embodiment (it may also include a cured product of a resin composition that does not correspond to the resin composition involved in the present embodiment). The second mode of the transparent antenna involved in the present embodiment comprises a transparent substrate (transparent component), a conductive component arranged on the transparent substrate, and a covering component arranged on the conductive component, and the covering component comprises a cured product of the resin composition involved in the present embodiment. In the transparent antenna involved in the second mode, the transparent substrate (transparent component) may include a cured product of the resin composition involved in the present embodiment, or may not include a cured product of the resin composition involved in the present embodiment (it may also include a cured product of a resin composition that does not correspond to the resin composition involved in the present embodiment). The transparent antenna according to the present embodiment may include a transparent substrate, a conductive member disposed on the transparent substrate, and a covering member disposed on the conductive member, wherein at least one selected from the group consisting of the transparent substrate and the covering member includes a cured product of the resin composition according to the present embodiment.

[0255] In the transparent antenna involved in this embodiment, the covering component can be arranged on at least a part (a part or all) of the conductive component. The covering component can be arranged on at least a part (a part or all) of the transparent substrate. In addition to the part arranged on the conductive component, the covering component can also have a part arranged on the transparent substrate but not arranged on the conductive component. The conductive component is arranged on a part of the transparent substrate (for example, a part of the main surface of the transparent substrate), so that the covering component (transparent component) can be arranged on the transparent substrate and the conductive component. The covering component can protect the conductive component by covering the conductive component. The covering component can protect the transparent substrate by covering the transparent substrate.

[0256] The covering member may abut against the conductive member. The covering member may abut against the transparent substrate or may not abut against the transparent substrate. The transparent substrate may abut against a transparent member different from the covering member (for example, a supporting member described later). The covering member may abut against a transparent member different from the transparent substrate (for example, a protective member described later).

[0257] In the transparent antenna involved in the present embodiment, at least one component selected from the group consisting of a transparent substrate and a covering component can contain a cured product of the resin composition involved in the present embodiment. In the case where one of the transparent substrate and the covering component (hereinafter referred to as "component A") does not contain a cured product of the resin composition involved in the present embodiment, component A can be formed of a material having a total light transmittance of 90% or more or 91% or more per 8 μm thickness. As the constituent material of component A, polyolefins (polyethylene, polypropylene, cycloolefin polymer (COP), etc.), polyesters (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, etc.), polycarbonate, polyamide, polyimide, polyamideimide, polyetherimide, polyether sulfide, polyether sulfone, polyether ketone, polyphenylene ether, polyphenylene sulfide, etc. can be cited. For example, component A can contain a cycloolefin polymer.

[0258] In the transparent antenna involved in this embodiment, as the structure of the conductive component, the above-mentioned structure can be used for the conductive component in the laminated body involved in the second embodiment. For example, the conductive component can contain copper. The conductive component can be solid or have a patterned (e.g., mesh) portion. The conductive component can be a single layer. As the thickness of the transparent substrate, the above-mentioned thickness can be used for the transparent resin layer of the laminated body involved in this embodiment.

[0259] The transparent antenna involved in this embodiment may include a supporting member supporting a transparent substrate, that is, it may include a supporting member, a transparent substrate arranged on the supporting member, and a conductive member arranged on the transparent substrate. The transparent antenna involved in this embodiment may include a protective member arranged on a covering member, that is, it may include a transparent substrate, a conductive member arranged on the transparent substrate, a covering member arranged on the conductive member, and a protective member arranged on the covering member.

[0260] The shapes of the supporting member and the protective member are not particularly limited, and may be film-shaped, substrate-shaped, indefinite, etc. As constituent materials of the supporting member and the protective member, resin materials, inorganic materials, etc. may be cited. As resin materials, polyolefins (polyethylene, polypropylene, cycloolefin polymers, etc.), polyesters (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, etc.), polycarbonates, polyamides, polyimides, polyamide-imides, polyetherimides, polyether sulfides, polyether sulfones, polyether ketones, polyphenylene ethers, polyphenylene sulfides, etc. may be cited. As inorganic materials, glass, etc. may be cited. The supporting member and the protective member are not limited to being transparent, and may be transparent members (transparent films, transparent substrates, etc.) or opaque members. The supporting member and the protective member may be formed of a material having a total light transmittance of more than 90% per a thickness of 8 μm. From the viewpoint of low dielectric, the supporting member may contain polyolefins.

[0261] The first mode of the method for manufacturing the transparent antenna involved in the present embodiment includes a covering component forming step of forming a covering component on a conductive component in a laminated body having a transparent resin layer (a transparent resin layer supporting a conductive component) and a conductive component arranged on the transparent resin layer, wherein at least one selected from the group consisting of the transparent resin layer and the covering component includes at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product. In the covering component forming step, the covering component can be formed by supplying at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product to the conductive component, or the covering component (transparent resin layer) can be formed by arranging the transparent resin layer of the laminated body involved in the present embodiment on the conductive component. When the laminated body involved in the present embodiment is used, the transparent resin layer of the laminated body involved in the present embodiment can be arranged on the conductive component after removing the substrate film or the protective film. The coating component forming step can be a step of forming a coating component comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product on a transparent resin layer and a conductive component in a stacked body comprising a transparent resin layer (a transparent resin layer supporting a conductive component) and a conductive component arranged on a part of the transparent resin layer (for example, a part of the main surface of the transparent resin layer).

[0262] The manufacturing method of the transparent antenna involved in the first embodiment may include a curing step of curing the coating component (resin composition of the coating component) to obtain a cured product before the coating component forming process, after the coating component forming process, or before and after the coating component forming process. The manufacturing method of the transparent antenna involved in the first embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) supporting the conductive component to obtain a cured product (transparent substrate) before the coating component forming process, after the coating component forming process, or before and after the coating component forming process. The coating component and the transparent resin layer (transparent resin layer supporting the conductive component) can be cured in the same curing process. In the curing process, the uncured resin composition can be irradiated with active light to cure the resin composition, or the uncured resin composition can be heated to cure the resin composition. As active light, there is no particular limitation, but ultraviolet rays can be used, and ultraviolet rays with a wavelength of 365nm can also be used. The active light can be irradiated to the resin composition through a light-transmitting film (for example, a substrate film or a protective film of the laminated body involved in this embodiment). The curing step in another embodiment of the method for producing a transparent antenna described below may be the same as the curing step in the method for producing a transparent antenna according to the first embodiment.

[0263] In a second aspect of the method for manufacturing a transparent antenna according to the present embodiment, as a method for obtaining the transparent antenna according to the second aspect, a lamination step is included in which a laminated body having a conductive member and a coating member disposed on the conductive member is laminated on a transparent resin layer in a state where the conductive member in the laminated body is located closer to the transparent resin layer than the coating member, and at least one selected from the group consisting of a transparent resin layer and a coating member includes at least one selected from the group consisting of a resin composition according to the present embodiment and a cured product thereof. As the laminated body having a conductive member and a coating member disposed on the conductive member, the laminated body according to the second aspect can be used, and in the lamination step, the transparent resin layer in the laminated body according to the second aspect can be disposed as the coating member.

[0264] The manufacturing method of the transparent antenna involved in the second embodiment may include a curing step of curing the covering member (resin composition of the covering member) to obtain a cured product before the lamination step, after the lamination step, or before and after the lamination step. The manufacturing method of the transparent antenna involved in the second embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the lamination step, after the lamination step, or before and after the lamination step. The covering member and the transparent resin layer may be cured in the same curing step.

[0265] In the manufacturing method of the transparent antenna involved in the first embodiment and the second embodiment, the transparent resin layer and the conductive component are the same as the transparent resin layer and the conductive component described above with respect to the laminated body and the transparent antenna involved in this embodiment. The transparent resin layer can be supported by the supporting component. In addition to the part arranged on the conductive component, the covering component can also have a part arranged on the transparent resin layer but not arranged on the conductive component, and can also abut against the transparent substrate and the conductive component.

[0266] The third method of manufacturing the transparent antenna involved in the present embodiment includes a processing step of patterning (e.g., processing into a mesh) at least a portion of a conductive component (solid conductive component) disposed on a transparent resin layer (including at least one transparent resin layer selected from the group consisting of the resin composition involved in the present embodiment and its cured product). In the processing step, a patterned (e.g., mesh-shaped) conductive component can be obtained by etching the conductive component in a state where a patterned resist layer is disposed on the conductive component of a laminate having a transparent resin layer and a conductive component disposed on the transparent resin layer. The resist layer can be removed after etching the conductive component. The patterned resist layer can be obtained by removing the uncured portion or the cured portion of the photosensitive layer (a layer including a photosensitive composition) disposed on the conductive component. For example, the patterned resist layer can be obtained by irradiating (exposing) a photosensitive layer (a layer containing a photosensitive composition) disposed on a conductive member with active light (e.g., ultraviolet rays), and then removing (developing) the unexposed portion (when the photosensitive layer has negative photosensitivity) or the exposed portion (when the photosensitive layer has positive photosensitivity). As the photosensitive layer, the above-mentioned layer L can be used.

[0267] The laminate having a conductive component disposed on a transparent resin layer can be obtained by forming a conductive component on a transparent resin layer (for example, a transparent resin layer containing at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product), for example, after removing the protective film of the laminate involved in the first embodiment, the conductive component is formed on the transparent resin layer. The laminate having a conductive component disposed on a transparent resin layer may be the laminate involved in the second embodiment.

[0268] The method for manufacturing a transparent antenna according to the third embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the processing step, after the processing step, or before or after the processing step. The method for manufacturing a transparent antenna according to the third embodiment may include a covering member forming step of forming a covering member on the conductive member after the processing step, and may also include a step of disposing a protective member (e.g., a transparent member) on the covering member.

[0269] The fourth mode of the method for manufacturing the transparent antenna involved in the present embodiment includes a formation process of forming a patterned (e.g., mesh-shaped) conductive component in a state where a patterned resist layer is arranged on a transparent resin layer (e.g., a transparent resin layer containing at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product). In the formation process, the resist layer can be used as a mask, and the patterned (e.g., mesh-shaped) conductive component can be formed by plating or sputtering. The resist layer can be removed after the formation process. The method for manufacturing the transparent antenna involved in the fourth mode may include a curing process of curing the transparent resin layer (resin composition of the transparent resin layer) before the formation process, after the formation process, or before and after the formation process to obtain a cured product (transparent substrate). The method for manufacturing the transparent antenna involved in the fourth mode may include a coating component forming process of forming a coating component on the conductive component after the formation process, and may also include a process of configuring a protective component (e.g., a transparent component) on the coating component.

[0270] The fifth mode of the method for manufacturing the transparent antenna involved in the present embodiment includes a removal step of removing the substrate film in the laminate involved in the second mode. The conductive component in the laminate involved in the second mode may have a patterned (e.g., mesh-like) portion. In the case where the transparent resin layer of the laminate during the removal step contains a cured product (in the case where the transparent resin layer is a transparent substrate), a laminate of a transparent substrate and a conductive component (a patterned (e.g., mesh-like) conductive component, etc.) can be obtained as a part of the transparent antenna through the removal step. The method for manufacturing the transparent antenna involved in the fifth mode may include a curing step of curing the transparent resin layer (the resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the removal step, after the removal step, or before and after the removal step. The method for manufacturing the transparent antenna involved in the fifth mode may include a covering component forming step of forming a covering component on the conductive component after the removal step, and may also include a step of configuring a protective component (e.g., a transparent component) on the covering component.

[0271] The sixth mode of the method for manufacturing the transparent antenna involved in the present embodiment includes a lamination step of laminating the transparent resin layer in the laminated body involved in the present embodiment on a supporting member. As the supporting member, the above-mentioned supporting member can be used for the transparent antenna. In the lamination step, the transparent resin layer can be laminated on the supporting member in a state where the base film in the laminated body involved in the present embodiment is removed, or the transparent resin layer can be laminated on the supporting member in a state where the protective film in the laminated body involved in the first mode is removed. The method for manufacturing the transparent antenna involved in the sixth mode may include a removal step A of removing the base film in the laminated body involved in the present embodiment, and may also include a removal step B of removing the protective film in the laminated body involved in the first mode.

[0272] In the case of using the laminated body involved in the second embodiment, in the lamination process, the transparent resin layer and the conductive component can be laminated on the supporting component in a state where the transparent resin layer is located closer to the supporting component than the conductive component, or the transparent resin layer and the conductive component can be laminated on the supporting component in a state where the transparent resin layer is in contact with the supporting component. In the lamination process, the conductive component can be solid or have a patterned (e.g., mesh) portion. In the lamination process, the transparent resin layer and the conductive component can be laminated on the supporting component in a state where the base film in the laminated body involved in the second embodiment is removed. In the case where the laminated body involved in the second embodiment has a protective film disposed on the conductive component, in the lamination process, the transparent resin layer, the conductive component and the protective film can be laminated on the supporting component in a state where the transparent resin layer is located closer to the supporting component than the conductive component (the conductive component is located closer to the transparent resin layer than the protective film). When the laminated body according to the second aspect includes a base film, a transparent resin layer, a conductive member, and a protective film, the method for manufacturing a transparent antenna according to the sixth aspect may include a removal step B of removing the protective film after the removal step A and the lamination step. When the laminated body according to the second aspect includes the above-mentioned layer L, in the lamination step, the transparent resin layer, the conductive member, and the layer L may be laminated on the support member in a state where the transparent resin layer is located closer to the support member than the conductive member.

[0273] In the case where the supporting member and the conductive member are stacked with good adhesion in a laminate having a supporting member and a conductive member arranged on the supporting member, surface treatment (plasma treatment, corona treatment, etc.) is sometimes applied to the supporting member, and the manufacturing process of the laminate may become complicated. For example, when polyolefin is used as the constituent material of the supporting member, since the adhesion between polyolefin and the conductive member (for example, metal materials such as copper) is low, surface treatment is sometimes required to obtain sufficient adhesion. On the other hand, according to the manufacturing method of the transparent antenna involved in the sixth embodiment, sufficient adhesion between the supporting member and the conductive member is obtained through the transparent substrate, and at the same time, a laminate of the supporting member and the conductive member (a laminate having a supporting member, a transparent substrate and a conductive member) can be obtained as a transparent antenna. For example, sufficient adhesion between the supporting member containing polyolefin and the conductive member containing copper can be obtained through the transparent substrate, and at the same time, a transparent antenna can be obtained. Furthermore, according to the manufacturing method of the transparent antenna involved in the sixth embodiment, by laminating the laminated body involved in the second embodiment on the supporting member, the transparent resin layer and the conductive member can be supplied to the supporting member together, and each component does not need to be formed on the supporting member each time the transparent antenna is manufactured, and the transparent antenna can be obtained by a simple method. In the case where the laminated body involved in the second embodiment has the above-mentioned layer L, according to the manufacturing method of the transparent antenna involved in the sixth embodiment, by laminating the laminated body involved in the second embodiment on the supporting member, the transparent resin layer, the conductive member and the layer L can be supplied to the supporting member together, and each component does not need to be formed on the supporting member each time the transparent antenna is manufactured, and the transparent antenna can be obtained by a simple method. In addition, according to the manufacturing method of the transparent antenna involved in the sixth embodiment, as the constituent material of the transparent resin layer or the transparent substrate, by using a material having excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.), a transparent antenna having excellent antenna characteristics can be obtained.

[0274] In the method for producing a transparent antenna according to the sixth aspect, the transparent resin layer in the removal step A, the removal step B, and the lamination step may be uncured or may be a cured product. The method for producing a transparent antenna according to the sixth aspect may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the removal step A, before the removal step B, before the lamination step, after the removal step A, after the removal step B, after the lamination step, before and after the removal step A, before and after the removal step B, or before and after the lamination step.

[0275] In the method for manufacturing a transparent antenna according to the sixth embodiment, the conductive component in the removal step A, the removal step B, and the stacking step may be solid or may have a patterned (e.g., mesh-like) portion. When the conductive component is solid, the method for manufacturing a transparent antenna according to the sixth embodiment may include a processing step A of patterning at least a portion of the conductive component (e.g., processing into a mesh) after the stacking step. In the processing step A, a patterned resist layer may be used as a mask to pattern at least a portion of the conductive component by etching at least a portion of the conductive component. The method in which the conductive component has a patterned portion in the stacking step may be as follows: the method for manufacturing a transparent antenna according to the sixth embodiment includes a stacking step in which the transparent resin layer in a stack having a transparent resin layer and a conductive component disposed on the transparent resin layer is located on a support member side more than the conductive component, the transparent resin layer comprises at least one selected from the group consisting of the resin composition and its cured product according to the present embodiment, and the conductive component has a patterned portion.

[0276] When the laminated body according to the second embodiment includes the layer L, the method for manufacturing a transparent antenna according to the sixth embodiment may include a processing step B of obtaining a patterned layer L (resist layer) by patterning at least a portion of the layer L after the lamination step and before the processing step A. In the processing step B, at least a portion of the layer L can be patterned by removing (developing) an unexposed portion (when the layer L has negative photosensitivity) or an exposed portion (when the layer L has positive photosensitivity), and after exposing the layer L, the unexposed portion or the exposed portion is removed (developed), thereby patterning at least a portion of the layer L. The method for manufacturing a transparent antenna according to the sixth embodiment may include a step of exposing at least a portion of the layer L before the lamination step. As a mode using a laminate having a layer comprising at least one selected from the group consisting of a photosensitive composition and a cured product thereof, the following mode may be used: the method for manufacturing a transparent antenna involved in the sixth mode includes a lamination step of laminating the laminate on a supporting member in a state in which the first layer in the laminate having a first layer, a second layer, and a conductive member arranged between the first layer and the second layer is located closer to the supporting member than the second layer, the first layer comprises at least one selected from the group consisting of the resin composition involved in this embodiment and a cured product thereof, and the second layer comprises at least one selected from the group consisting of a photosensitive composition and a cured product thereof.

[0277] In the method for manufacturing a transparent antenna according to the sixth embodiment, the conductive component in the removal step A, the removal step B, and the lamination step may be a multilayer, or may include a first conductive component disposed on a transparent resin layer, and a second conductive component disposed on the first conductive component. At least one selected from the group consisting of the first conductive component and the second conductive component may be solid, or may include a patterned (e.g., mesh-like) portion. At least one selected from the group consisting of the first conductive component and the second conductive component may contain copper. When the conductive component includes the first conductive component and the second conductive component, in the lamination step, the transparent resin layer and the conductive component may be laminated on the supporting component in a state where the first conductive component is located closer to the supporting component than the second conductive component. The method for manufacturing a transparent antenna according to the sixth embodiment may include a removal step C of removing the second conductive component after the lamination step. In the removal step C, the second conductive component can be peeled off from the first conductive component. The method for manufacturing a transparent antenna according to the sixth embodiment may include a processing step of patterning (e.g., processing into a mesh) at least a portion of the first conductive component after the removal step C. In the processing step, for example, the first conductive member may be etched while a patterned resist layer is disposed on the first conductive member. The method for manufacturing a transparent antenna according to the sixth aspect may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the removal step C, after the removal step C, or before and after the removal step C.

[0278] The manufacturing method of the transparent antenna involved in the sixth embodiment may include a covering component forming step of forming a covering component on the conductive component before the lamination step, after the lamination step, or before and after the lamination step, and may also include a step of configuring a protective component (such as a transparent component) on the covering component.

[0279] The seventh mode of the method for manufacturing a transparent antenna involved in the present embodiment is a method for manufacturing a transparent antenna using a laminate (the laminate involved in the second mode) comprising the above-mentioned substrate film, the above-mentioned transparent resin layer (for example, a transparent resin layer comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product), and the above-mentioned conductive component having a first conductive component and a second conductive component, and the manufacturing method comprises a removal step C of removing the second conductive component in a state where the transparent resin layer in the laminate involved in the second mode is located closer to the supporting component side than the conductive component and the transparent resin layer and the conductive component are stacked on the supporting component.

[0280] The manufacturing method of the transparent antenna involved in the seventh embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the removal step C, after the removal step C, or before and after the removal step C in a state where the transparent resin layer and the conductive component are stacked on the supporting component. In the curing step, the transparent resin layer may be cured in a state where the transparent resin layer and the conductive component are stacked on the supporting component while the transparent resin layer is located closer to the supporting component than the conductive component. The manufacturing method of the transparent antenna involved in the seventh embodiment may include a processing step of patterning (for example, processing into a mesh shape) at least a portion of the first conductive component after removing the second conductive component (after the removal step C). An example of a method for manufacturing a transparent antenna according to the seventh embodiment is a method for manufacturing a laminated body including the substrate film, the transparent resin layer (a transparent resin layer containing an uncured resin composition), and the conductive member having the first conductive member and the second conductive member as the laminated body according to the second embodiment, the manufacturing method comprising the removal step A (first removal step), a lamination step, a curing step, and a removal step C (second removal step). In the method for manufacturing a transparent antenna according to the seventh embodiment, at least one selected from the group consisting of the first conductive member and the second conductive member may contain copper. Furthermore, the first conductive member in the laminated body may be solid or may have a patterned (e.g., meshed) portion.

[0281] The eighth mode of the method for manufacturing a transparent antenna according to the present embodiment includes a removal step B of removing the protective film in a state where a transparent resin layer (for example, a transparent resin layer comprising at least one selected from the group consisting of the resin composition according to the present embodiment and its cured product), a conductive component and a protective film are sequentially stacked on a supporting component. In this case, the laminate may be, for example, a single-layer conductive component, and a demolding treatment is applied to at least a portion of one surface of the conductive component side of the protective film. The method for manufacturing a transparent antenna according to the eighth mode may include: a removal step A of removing the substrate film in the laminate according to the second mode before the removal step B; and a stacking step of stacking the transparent resin layer, the conductive component and the protective film on the supporting component. The method for manufacturing a transparent antenna according to the eighth mode may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) before the removal step B, after the removal step B, or before and after the removal step B to obtain a cured product (transparent substrate).

[0282] The method for manufacturing the transparent antenna according to the eighth aspect may include a covering member forming step of forming a covering member on the conductive member after the removing step C, and may include a step of disposing a protective member (eg, a transparent member) on the covering member.

[0283] In the manufacturing method of the transparent antenna involved in the above-mentioned 1st to 8th aspects, the above-mentioned steps, structures, etc. can be combined with each other for each aspect. For example, in the manufacturing method of the transparent antenna involved in the 7th aspect, the manufacturing method of the transparent antenna involved in the 6th aspect can use the above-mentioned steps, structures, etc.

[0284] The transparent antenna involved in this embodiment can be used in an image display device, a car component (windshield, rear window glass, sunroof, window, etc.), a building, etc. The image display device, car or building involved in this embodiment has the transparent antenna involved in this embodiment. The image display device can have an image display portion for displaying an image, and a frame portion (frame portion) located around the image display portion, and the transparent antenna can be arranged on the image display portion. The image display device can be used in various electronic devices such as personal computers, navigation systems (such as car navigation), mobile phones, clocks, electronic dictionaries, etc.

[0285] Figure 3 and Figure 4 It is a schematic cross-sectional view showing an example of an image display device, and shows a part of an image display portion of the image display device. Figure 3 The image display device 100 includes a transparent antenna 110 and a protective member 120 disposed on the transparent antenna 110. The transparent antenna 110 includes a transparent substrate 110a, a mesh conductive member 110b disposed on the transparent substrate 110a, and a covering member 110c disposed on the transparent substrate 110a and the conductive member 110b. Figure 4 The image display device 200 includes a transparent antenna 210 and a protective member 220 disposed on the transparent antenna 210. The transparent antenna 210 includes a transparent member 210a, a transparent substrate 210b disposed on the transparent member 210a, a mesh conductive member 210c disposed on the transparent substrate 210b, and a covering member 210d disposed on the transparent substrate 210b and the conductive member 210c. The covering members 110c and 210d cover the transparent substrates 110a and 210b and the conductive members 110b and 210c.

[0286] In the image display device 100, at least one selected from the group consisting of the transparent substrate 110a and the covering member 110c includes a cured product of the resin composition involved in the present embodiment, for example, it is formed by the cured product of the resin composition involved in the present embodiment. One of the transparent substrate 110a and the covering member 110c can be formed by a material having a total light transmittance of more than 90% per 8μm thickness (for example, a polyolefin such as a cycloolefin polymer). In the image display device 200, at least one selected from the group consisting of the transparent substrate 210b and the covering member 210d includes a cured product of the resin composition involved in the present embodiment, for example, it is formed by the cured product of the resin composition involved in the present embodiment. One of the transparent substrate 210b and the covering member 210d can be formed by a material having a total light transmittance of more than 90% per 8μm thickness. The conductive members 110b and 210c are formed, for example, of copper. The transparent member 210a is formed, for example, of polyolefin. The protective members 120 and 220 can be, for example, glass plates.

[0287] [Example]

[0288] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0289] <Preparation of resin varnish>

[0290] (Example 1)

[0291] While stirring, 80 parts by mass (solid content) of polymer 1 (maleic anhydride-modified styrene-butadiene-styrene block copolymer, styrene-butadiene elastomer, styrene / butadiene mass ratio = 40 / 60, manufactured by ASAHI KASEI CORPORATION, product name: Tuffprene 912), 20 parts by mass of acrylic compound (acrylic monomer, 1,9-nonanediol diacrylate, manufactured by OSAKA ORGANIC CHEMICAL INDUSTRY LTD, product name: Viscoat #260), 1.5 parts by mass of photopolymerization initiator (photo radical generator, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, manufactured by IGM Resins BV, product name: Omnirad 819), and silane coupling agent (a siloxane compound having an organic group having a carboxyl group and bonded to a silicon atom, manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed. Co., Ltd., product name: X-12-1135) and 360 parts by mass of toluene (solvent) to obtain a resin varnish.

[0292] (Example 2)

[0293] A resin varnish was obtained in the same manner as in Example 1 except that 20 parts by mass of a propylene glycol monomethyl ether solution of tetrazole compound 1 (5-amino-1H-tetrazole) (5-amino-1H-tetrazole content: 5 mass%, manufactured by Chiyoda Chemical Co., Ltd., product name: B-6030) was further mixed (5-amino-1H-tetrazole: 1 mass part) and the amount of toluene (solvent) used was reduced.

[0294] (Example 3)

[0295] A resin varnish was obtained in the same manner as in Example 1 except that 1 part by mass of tetrazole compound 2 (1-methyl-5-mercapto-1H-tetrazole, manufactured by TOYOBO CO., LTD., product name: MMT) was further mixed.

[0296] (Example 4)

[0297] A resin varnish was obtained in the same manner as in Example 3 except that the amount of polymer 1 used was changed to 85 parts by mass and the amount of the acrylic compound used was changed to 15 parts by mass.

[0298] (Comparative Example 1)

[0299] While stirring, 80 parts by mass of polymer 2 (random copolymer, styrene-butadiene elastomer, manufactured by JSR Corporation, product name: DYNARON 2324P), 20 parts by mass of acrylic compound (manufactured by OSAKA ORGANIC CHEMICAL INDUSTRY LTD, product name: Viscoat #260), 1.5 parts by mass of photopolymerization initiator (manufactured by IGM Resins BV, product name: Omnirad 819) and 360 parts by mass of toluene (solvent) were mixed to obtain a resin varnish.

[0300] <Production of laminated films>

[0301] As a substrate film, a surface release-treated PET film (manufactured by FUJIMORI KOGYO CO., LTD., product name: HTA, thickness: 75 μm) was prepared. The above-mentioned resin varnish was applied to the release-treated surface of the PET film using a knife coater (manufactured by YASUI SEIKI CO., LTD., product name: SNC-300). Then, a resin film was formed by drying at 100° C. for 10 minutes in a dryer (manufactured by FUTABA KAGAKUIBARAKI CO., LTD., product name: MSO-80TPS). By adjusting the gap of the coater, the thickness of the dried resin film was adjusted to 8 μm. Next, as a protective film, a surface release-treated PET film (manufactured by FUJIMORI KOGYO CO., LTD., product name: BD, thickness: 75 μm) was prepared, and then a laminated film A was obtained by attaching the release-treated surface of the protective film to the above-mentioned resin film.

[0302] <Evaluation>

[0303] Adhesion, moisture and heat resistance, and dielectric properties were evaluated in the following order. Regarding moisture and heat resistance and dielectric properties, only the examples were evaluated, and the comparative examples were not evaluated. The results are shown in Table 1.

[0304] (Tightness)

[0305] The surface of the COP film (thickness: 100 μm) was plasma treated using a plasma treatment machine (manufactured by SAMCO Inc., product name: PC-300) under the conditions of "gas: oxygen, gas flow rate: 10 sccm, output: 100 W, treatment time: 3 minutes", thereby obtaining a plasma-treated COP film. Next, after peeling off the protective film of the above-mentioned laminated film A to expose the resin film, a manual roller was used to adhere the plasma-treated surface of the above-mentioned plasma-treated COP film to the resin film, thereby obtaining a laminated film B. Afterwards, an ultraviolet exposure machine (manufactured by MIKASA CO., LTD, product name: ML-320FSAT) was used to expose the resin film of the laminated film B from the plasma-treated COP film side at 2000 mJ / cm 2 The resin film was photocured by irradiating with ultraviolet rays (wavelength 365 nm). In addition, by peeling off the base film of the laminated film B, a laminated body A for evaluation (50 mm in length and 50 mm in width) was obtained.

[0306] Next, the adhesion of the resin film was evaluated using the method according to JIS K 5600-5-6. Specifically, first, the blade of the knife was pressed against the exposed surface of the resin film in the evaluation laminate A, and 11 cuts were made at intervals of 1 mm. Next, the evaluation laminate A was rotated 90 degrees, and 11 cuts were made at intervals of 1 mm. After that, a tape (manufactured by NICHIBAN CO., LTD., product name: CT405AP-24) was pressed by hand on the portion where the cut was made, so that the tape was in close contact with the portion where the cut was made on the resin film. Finally, the tape was peeled off, and the number of grids of the resin film remaining in the portion where the cut was made (a total of 100 grids) was counted. The adhesion was evaluated by performing a cross-cut test (25°C) in the above order.

[0307] (Moisture and heat resistance)

[0308] After exposing the release surface A by peeling off the light release isolation member (protective film) on one side of the OCA tape (manufactured by 3M Japan Limited, 8146, thickness: 75μm), the release surface A was bonded to the glass plate using a manual roller. Then, the release surface B was exposed by peeling off the heavy release isolation member (substrate film) on the other side of the above-mentioned OCA tape. Next, the release surface B was bonded to the surface from which the protective film of the above-mentioned laminated film A was peeled off using a manual roller. In addition, a COP film (thickness: 100μm) was bonded to the surface from which the substrate film of the laminated film A was peeled off using a manual roller, thereby obtaining a laminated film C. Afterwards, a UV exposure machine (manufactured by MIKASA CO., LTD, product name: ML-320FSAT) was used to expose the resin film of the laminated film C from the glass plate side at 2000mJ / cm 2 The resin film was photocured by irradiating with ultraviolet rays (wavelength: 365 nm), thereby obtaining a laminate B for evaluation (50 mm in length and 50 mm in width).

[0309] Next, as the moisture and heat resistance, the total light transmittance (TT) of the evaluation laminate B before and after exposure at 85°C and 85% RH for 100 hours was measured by a method in accordance with JIS K 7136. Specifically, a white LED light was irradiated from the glass plate side of the evaluation laminate B under an environment of 25°C, and the total light transmittance of the light transmitted through the evaluation laminate B was measured. NDH-5000 (product name) manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd. was used as a measuring apparatus.

[0310] (Dielectric properties)

[0311] After peeling off the protective film of the laminate film A, the resin film of the laminate film A was attached to a COP film (untreated, thickness: 100 μm) using a manual roller. Then, an ultraviolet exposure machine (manufactured by MIKASA CO., LTD, product name: ML-320FSAT) was used to expose the resin film from the COP film side at 2000 mJ / cm 2 The resin film was photocured by irradiating with ultraviolet rays (wavelength: 365 nm), thereby obtaining a laminate C for evaluation (80 mm in length and 80 mm in width).

[0312] Next, using a vector network analyzer (manufactured by Agilent Technologies Japan, Ltd., product name: E8364B) and a 10 GHz resonator (manufactured by EM labs, Inc., product name: CP531), the relative dielectric constant (Dk@10GHz) and dielectric loss tangent (Df@10GHz) of the entire evaluation laminate C were measured by the separated pillar dielectric resonator method (SPDR method) at 25°C. In addition, the relative dielectric constant and dielectric loss tangent of the above-mentioned substrate film (80 mm in length and 80 mm in width) were measured by the same method. By subtracting the measurement results of the substrate film from the measurement results of the evaluation laminate C, the relative dielectric constant and dielectric loss tangent of the laminate formed by the resin film (cured film) and the COP film were obtained.

[0313] [Table 1]

[0314] [Table 2]

[0315]

[0316] The cured product obtained by using the resin varnish of each of the above examples and following the following procedure has a high tensile elastic modulus (eg, a tensile elastic modulus of 50 MPa or more).

[0317] (1) A laminated film was obtained in the same manner as in the above-mentioned laminated film A except that the thickness of the resin film was changed to 100 μm.

[0318] (2) Using an ultraviolet exposure machine (manufactured by MIKASA CO., LTD., product name: ML-320FSAT), the resin film of the laminated film was exposed to ultraviolet light at 2000 mJ / cm 2 The resin film was photocured by irradiating with ultraviolet rays (wavelength: 365 nm), thereby obtaining an evaluation film including a base film, a cured film, and a protective film.

[0319] (3) A laminate having a length of 50 mm and a width of 10 mm was cut out from the evaluation film, and then the base film and the protective film of the laminate were removed to obtain a test piece.

[0320] (4) The stress-strain curve of the test piece was measured at 25°C using AUTOGRAPH (manufactured by Shimadzu Corporation, product name: EZ-S), and the tensile modulus was determined from the stress-strain curve. The distance between the chucks during the measurement was set to 20 mm, and the tensile speed was set to 50 mm / min. As the tensile modulus, the value was measured at a load of 0.5 N to 1.0 N.

[0321] Explanation of symbols

[0322] 10, 20, 30-laminate, 10a, 20a, 30a-base film, 10b, 20b, 30b-transparent resin layer, 10c-protective film, 20c, 30c, 30d, 110b, 210c-conductive component, 100, 200-image display device, 110, 210-transparent antenna, 110a, 210b-transparent base material, 110c, 210d-covering component, 120, 220-protective component, 210a-transparent component.

Claims

1. A resin composition comprising a styrene block copolymer, a (meth)acrylic compound and a polymerization initiator.

2. The resin composition according to claim 1, wherein The styrenic block copolymer includes a styrene-butadiene-styrene block copolymer.

3. The resin composition according to claim 1, wherein The content of the styrene block copolymer is 50% by mass or more based on the total mass of the resin composition.

4. The resin composition according to claim 1, wherein The (meth)acrylic compound includes a methacrylic compound.

5. The resin composition according to claim 1, wherein The (meth)acrylic compound includes alkanediol di(meth)acrylate.

6. The resin composition according to claim 1, wherein The (meth)acrylic compound includes alkanediol dimethacrylate.

7. The resin composition according to claim 1, wherein The (meth)acrylic compound includes a compound represented by the following general formula (I): In the formula, R 1 represents a group containing 9 or less carbon atoms and 2 or more oxygen atoms, R 2a and R 2b Each independently represents a hydrogen atom or a methyl group.

8. The resin composition according to claim 7, wherein The (meth)acrylic compound comprises R 2a and R 2b A compound wherein at least one of the radicals is a methyl group.

9. The resin composition according to claim 1, wherein The content of the (meth)acrylic compound is 1 to 300 parts by mass based on 100 parts by mass of the styrene block copolymer.

10. The resin composition according to claim 1, wherein The polymerization initiator comprises a peroxide.

11. The resin composition according to claim 1, wherein The polymerization initiator comprises a peroxy ester. 12 . A cured product, which is a cured product of the resin composition according to claim 1 .

13. A laminate comprising a substrate film and a transparent resin layer disposed on the substrate film, The transparent resin layer comprises at least one selected from the group consisting of the resin composition according to any one of claims 1 to 11 and a cured product thereof. The laminate according to claim 13 , further comprising a conductive member disposed on the transparent resin layer.

15. The laminate according to claim 14, wherein The conductive member contains copper.

16. The laminate according to claim 14, wherein The conductive member has a thickness of 5 μm or less.

17. A transparent antenna comprising a transparent substrate, a conductive component disposed on the transparent substrate, and a covering component disposed on the conductive component. At least one selected from the group consisting of the transparent substrate and the covering member comprises a cured product of the resin composition according to any one of claims 1 to 11.

18. The transparent antenna according to claim 17, wherein: The conductive member has a mesh portion.

19. The transparent antenna according to claim 17, wherein: The conductive member contains copper.

20. An image display device comprising the transparent antenna according to claim 17.